Agent for preventing scattering of dust and method for preventing scattering of dust
The dust shattering agent, composed of fibrous cellulose with a fiber width of 1000 nm or less and an ionic substituent, addresses the inadequacies of existing agents by achieving an effective dust shattering effect, suppressing dust generation, and ensuring environmental safety.
Patent Information
- Application Number
- JP2025011787
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-03-26
- Filing Date
- 2025-01-28
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-03-26
AI Technical Summary
Existing dust shattering agents are inadequate in achieving an effective dust shattering effect, leading to insufficient suppression of dust generation at construction, waste disposal, and development sites.
A dust shattering agent is developed by blending fibrous cellulose with a fiber width of 1000 nm or less, along with a solvent, to enhance the dust shattering effect. The fibrous cellulose has an aspect ratio of 10 or more and may include an ionic substituent, such as a phosphorus oxo acid group, to improve dispersibility and binding strength.
The proposed dust shattering agent effectively suppresses dust generation by binding sediment particles, reducing the scattering of ultrafine particles like PM2.5, and exhibiting excellent spray properties, making it environmentally friendly and suitable for natural environments.
Smart Images

Figure 2025061862000006 
Figure 2025061862000007 
Figure 2025061862000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a dust-preventing agent and a dust-preventing method. [Background technology]
[0002] In the past, there was a problem of dust being generated by the wind at construction sites, waste disposal sites, reclaimed land, etc., which has a negative impact on the surrounding environment. For this reason, various measures to prevent dust generation, such as water sprinkling dust suppression and dust covering suppression, have been considered.
[0003] For example, Patent Document 1 describes a dust dispersion suppressant containing a chitosan solution. Patent Document 1 discusses the use of a solution in which chitosan and acetic acid are diluted in a weight ratio of 6:4, with the chitosan solution having a concentration of 5,000 ppm to 20,000 ppm, as a dust dispersion suppressant.
[0004] Patent Document 2 discloses a dust suppressant containing 0.1-7% latex, 0.1-6% modified starch / modified cellulose, 0.1-5% sodium alginate, 0.1-8% polyvinyl alcohol, 0-8% sodium silicate, 10-60% glycerin, 0.01-5% surfactant, and the remainder water. The modified cellulose in Patent Document 2 is an amorphous water-soluble cellulose derivative. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2011-190398 A [Patent Document 2] Special Publication No. 2019-513155 Summary of the Invention [Problem to be solved by the invention]
[0006] The present inventors have studied conventional dust dispersion inhibitors and found that there is room for improvement in the dust dispersion inhibitor effect. In order to solve such problems of the conventional techniques, the present inventors have carried out research with the aim of providing a dust dispersion inhibitor capable of exhibiting excellent dust dispersion inhibitor effect. [Means for solving the problem]
[0007] As a result of intensive research aimed at solving the above problems, the present inventors have found that by blending a dust-scattering prevention agent with fibrous cellulose having a fiber width of 1000 nm or less, a dust-scattering prevention agent capable of exhibiting excellent dust-scattering prevention effect can be obtained. Specifically, the present invention has the following configuration.
[0008] [1] A dust-suppressing agent comprising a solvent and fibrous cellulose having a fiber width of 1,000 nm or less. [2] The dust-proofing agent according to [1], wherein the aspect ratio of the fibrous cellulose is 10 or more. [3] The dust-suppressing agent according to [1] or [2], in which an ionic substituent is introduced into the fibrous cellulose. [4] The dust-suppressing agent according to [3], wherein the ionic substituent is an anionic group. [5] The dust-suppressing agent according to [3], wherein the ionic substituent is at least one selected from the group consisting of a phosphorus oxoacid group, a substituent derived from a phosphorus oxoacid group, a carboxy group, a substituent derived from a carboxy group, a carboxymethyl group, a carboxyethyl group, a sulfur oxoacid group, a substituent derived from a sulfur oxoacid group, a sulfone group, a substituent derived from a sulfone group, and an ammonium group. [6] The dust-preventing agent according to any one of [1] to [5], wherein the solid content concentration of the fibrous cellulose is 1.0 mass % or less. [7] The dust-suppressing agent according to any one of [1] to [6], which has a pH of 5.0 or more and 9.0 or less. [8] The dust-suppressing agent according to any one of [1] to [7], wherein the solvent is a solvent mainly composed of water. [9] A method for preventing scattering of dust, comprising a step of spraying the dust-scattering inhibitor according to any one of [1] to [8] onto a dust-generating object. Effect of the Invention
[0009] According to the present invention, a dust-preventing agent capable of exerting an excellent dust-preventing effect can be obtained. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having phosphorus oxoacid groups and pH. [Diagram 2] FIG. 2 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having a carboxy group and pH. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below. The following description of the components may be based on representative embodiments or specific examples, but the present invention is not limited to such embodiments.
[0012] (Dust prevention agent) The present invention relates to a dust dispersion inhibitor containing a solvent and fibrous cellulose having a fiber width of 1000 nm or less. In this specification, the fibrous cellulose having a fiber width of 1000 nm or less is also called fine fibrous cellulose or CNF.
[0013] The dust dispersion inhibitor of the present invention has the above-mentioned constitution, and therefore exhibits an excellent dust dispersion prevention effect. Specifically, when the dust dispersion inhibitor of the present invention is sprayed on a dust-generating object such as soil and sand, which is a dust generating source, the soil and sand can be bound. As a result, dust generation can be suppressed. This is presumably because, by scattering the fine fibrous cellulose on the dust-generating object, the particles of the dust-generating object are firmly bound by the crystalline fine fibrous cellulose. In addition, the dust dispersion inhibitor of the present invention can also suppress the dispersion of ultrafine particles such as PM2.5.
[0014] The dust scattering prevention effect can be confirmed, for example, by evaluating the binding strength of silica sand by the following method. First, 5 g of silica sand No. 6 (manufactured by Toyo Matheran Co., Ltd.) is used as a model substance that generates dust, and is laid in a circular shape with a diameter of 50 mm. Next, 7 g of dust scattering prevention agent is sprayed onto the dust-generating object of this silica sand, and it is dried at room temperature for 24 hours. Then, when the center of the dust-generating object is pressed with a load of 2 N, if the surface of the silica sand does not collapse and the occurrence of cracks is suppressed, it can be determined that the silica sand is well bound. If the silica sand is well bound, dust does not scatter even when air is blown onto the bound body, and it can be determined that the dust scattering prevention effect is exerted by spraying the dust scattering prevention agent.
[0015] In addition, the dust dispersion inhibitor of the present invention has the above-mentioned composition and therefore has excellent spray characteristics. Since the dust dispersion inhibitor of the present invention contains fine fibrous cellulose having a fiber width of 1000 nm or less, the nozzle is not clogged with solid matter even when the dust dispersion inhibitor is sprayed, and therefore it is possible to spray coat the dust-generating object uniformly and continuously.
[0016] Furthermore, since the dust dispersion inhibitor of the present invention contains fine fibrous cellulose obtained by micronizing plant-derived cellulose, the dust dispersion inhibitor contains plant-derived raw materials. Therefore, even if the dust dispersion inhibitor of the present invention is sprayed in a natural environment such as soil, it does not chemically contaminate the soil or adversely affect the properties of the soil. Thus, the dust dispersion inhibitor of the present invention has a low environmental load and can be said to be an environmentally friendly agent.
[0017] In this embodiment, the pH of the dust dispersion inhibitor is preferably 5.0 or more, more preferably 5.5 or more, and even more preferably 6.0 or more. The pH of the dust dispersion inhibitor is preferably 9.0 or less. In this way, the pH of the dust dispersion inhibitor is preferably in the near-neutral region. By making the pH of the dust dispersion inhibitor in the near-neutral region, for example, even when the dust dispersion inhibitor is sprayed into a natural environment such as soil, the pH of the soil is not changed, and adverse effects on the ecosystem can be suppressed.
[0018] In this embodiment, the solid content concentration of the fine fibrous cellulose is preferably 1.0 mass% or less, more preferably 0.8 mass% or less, and even more preferably 0.6 mass% or less, based on the total mass of the dust scattering inhibitor. The solid content concentration of the fine fibrous cellulose is preferably 0.01 mass% or more, based on the total mass of the dust scattering inhibitor. Thus, the solid content concentration of the fine fibrous cellulose in the dust scattering inhibitor may be low. Even when the active ingredient is in such a low concentration, the dust scattering inhibitor of the present invention can exhibit excellent dust scattering prevention effect.
[0019] In this embodiment, the dust dispersion inhibitor is preferably a water-based dust dispersion inhibitor. Here, the water-based dust dispersion inhibitor refers to an agent that contains water as a solvent as a main component. By containing water as a solvent as a main component, for example, even if the dust dispersion inhibitor is sprayed into a natural environment such as soil, it is possible to suppress adverse effects on the ecosystem without changing the properties of the soil.
[0020] (Fine fibrous cellulose) The dust dispersion inhibitor of the present invention contains fibrous cellulose having a fiber width of 1000 nm or less (fine fibrous cellulose). In this specification, the fibrous cellulose having a fiber width of 1000 nm or less (fine fibrous cellulose) also includes cellulose nanocrystal (CNC).
[0021] The fiber width of the fibrous cellulose may be 1000 nm or less, preferably 100 nm or less, more preferably 20 nm or less, and even more preferably 8 nm or less. The number-average fiber width of the fibrous cellulose contained in the dust scattering inhibitor is preferably 1000 nm or less. The number-average fiber width of the fibrous cellulose is, for example, preferably 2 nm or more and 1000 nm or less, more preferably 2 nm or more and 100 nm or less, even more preferably 2 nm or more and 50 nm or less, and particularly preferably 2 nm or more and 10 nm or less. The fibrous cellulose is, for example, a single fiber cellulose.
[0022] The fiber width of fibrous cellulose is measured, for example, using an electron microscope as follows. First, an aqueous suspension of fibrous cellulose with a concentration of 0.05% by mass or more and 0.1% by mass or less is prepared, and this suspension is cast on a hydrophilically treated carbon film-coated grid to prepare a sample for TEM observation. When wide fibers are included, an SEM image of the surface cast on glass may be observed. Next, observation is performed using an electron microscope image at a magnification of 1000x, 5000x, 10000x, or 50000x depending on the width of the fiber to be observed. However, the sample, observation conditions, and magnification are adjusted to satisfy the following conditions.
[0023] (1) A straight line X is drawn at any point within the observed image, and 20 or more fibers intersect with the straight line X. (2) Within the same image, draw a line Y that intersects the line perpendicularly, and 20 or more fibers intersect the line Y.
[0024] For the observation images that satisfy the above conditions, the width of the fibers that intersect with the lines X and Y is visually read. In this manner, three or more sets of observation images of at least the surface portions that do not overlap each other are obtained. Next, for each image, the width of the fibers that intersect with the lines X and Y is read. In this manner, the width of at least 20 fibers x 2 x 3 = 120 fibers is read. The average of the read fiber widths is then determined as the number average fiber width of the fibrous cellulose.
[0025] The fiber length of the fibrous cellulose is not particularly limited, but is preferably 0.1 μm or more and 1000 μm or less, more preferably 0.1 μm or more and 800 μm or less, and even more preferably 0.1 μm or more and 600 μm or less. By setting the fiber length within the above range, destruction of the crystalline region of the fibrous cellulose can be suppressed. In addition, it is also possible to set the slurry viscosity of the fibrous cellulose to an appropriate range. The fiber length of the fibrous cellulose can be determined, for example, by image analysis using TEM, SEM, or AFM.
[0026] The fibrous cellulose preferably has an I-type crystal structure. Here, the fact that the fibrous cellulose has an I-type crystal structure can be identified from a diffraction profile obtained from a wide-angle X-ray diffraction photograph using CuKα (λ=1.5418 Å) monochromatized with graphite. Specifically, it can be identified from the presence of typical peaks at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°. The proportion of I-type crystal structure in the fine fibrous cellulose is, for example, preferably 30% or more, more preferably 40% or more, and even more preferably 50% or more. This can be expected to provide even better performance in terms of heat resistance and low linear thermal expansion coefficient. In addition, since the fibrous cellulose has an I-type crystal structure, natural cellulose can be used as a raw material, and a dust scattering inhibitor with less environmental impact can be obtained. The degree of crystallinity can be determined by measuring an X-ray diffraction profile and determining the pattern by a conventional method (Seagal et al., Textile Research Journal, Vol. 29, p. 786, 1959).
[0027] The aspect ratio of the fibrous cellulose is preferably 10 or more, more preferably 20 or more, even more preferably 30 or more, even more preferably 40 or more, and particularly preferably 50 or more. The aspect ratio of the fibrous cellulose is preferably 10,000 or less, more preferably 1,000 or less. In this specification, the aspect ratio of the fibrous cellulose is the value of the axial ratio (fiber length / fiber width) of the fibrous cellulose. By setting the aspect ratio of the fibrous cellulose within the above range, the particles of the dust-generating object are easily firmly bound together, and the dust scattering prevention effect of the dust scattering prevention agent can be more effectively improved. In addition, by setting the aspect ratio of the fibrous cellulose within the above range, the spray characteristics (atomization characteristics) of the dust scattering prevention agent can be further improved.
[0028] The fibrous cellulose in this embodiment has, for example, both crystalline and non-crystalline regions. Fine fibrous cellulose having both crystalline and non-crystalline regions and having an aspect ratio within the above range is realized by the method for producing fine fibrous cellulose described below.
[0029] The fibrous cellulose of the present invention preferably has an ionic substituent. The ionic substituent may include, for example, either one or both of an anionic group and a cationic group. In this embodiment, it is particularly preferable that the ionic substituent has an anionic group. In addition, the ionic substituent is preferably a group that is introduced into the fibrous cellulose via an ester bond or an ether bond, and more preferably a group that is introduced into the fibrous cellulose via an ester bond. In this case, the ester bond is preferably formed by dehydration condensation of the fibrous cellulose and a compound that becomes an ionic substituent.
[0030] Examples of the anionic group as the ionic substituent include a phosphorus oxo acid group or a substituent derived from a phosphorus oxo acid group (sometimes simply referred to as a phosphorus oxo acid group), a carboxy group or a substituent derived from a carboxy group (sometimes simply referred to as a carboxy group), a carboxymethyl group, a carboxyethyl group, a sulfur oxo acid group or a substituent derived from a sulfur oxo acid group, a xanthate group or a substituent derived from a xanthate group, a phosphonic group or a substituent derived from a phosphonic group, a phosphine group or a substituent derived from a phosphine group, a sulfonic group or a substituent derived from a sulfonic group, a carboxyalkyl group, etc. Examples of the cationic group as the ionic substituent include an ammonium group, a phosphonium group, a sulfonium group, etc. Among them, the ionic substituent is preferably at least one selected from the group consisting of phosphorus oxo acid group, a substituent derived from a phosphorus oxo acid group, a carboxy group, a substituent derived from a carboxy group, a carboxymethyl group, a carboxyethyl group, a sulfur oxo acid group, a substituent derived from a sulfur oxo acid group, a sulfone group, a substituent derived from a sulfone group, and an ammonium group, more preferably at least one selected from the group consisting of phosphorus oxo acid group, a substituent derived from a phosphorus oxo acid group, a carboxy group, a substituent derived from a carboxy group, a carboxymethyl group, a sulfur oxo acid group, and a substituent derived from a sulfur oxo acid group, further preferably at least one selected from the group consisting of phosphorus oxo acid group, a substituent derived from a phosphorus oxo acid group, a carboxy group, and a substituent derived from a carboxy group, and particularly preferably at least one selected from phosphorus oxo acid group and a substituent derived from a phosphorus oxo acid group. By introducing a phosphorus oxo acid group as an anionic group, for example, even under alkaline or acidic conditions, the dispersibility of the fibrous cellulose can be further improved, and as a result, the dust scattering prevention effect of the dust scattering prevention agent can be more effectively improved.
[0031] The phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group is, for example, a substituent represented by the following formula (1). A plurality of substituents represented by the following formula (1) may be introduced into each fibrous cellulose. In this case, the plurality of introduced substituents represented by the following formula (1) may be the same or different.
[0032] [ka]
[0033] In formula (1), a, b, and n are natural numbers, and m is an arbitrary number (where a=b×m). At least one of the n α and α' is O. - and the rest are R or OR. Note that all of α and α' are O - The n α's may all be the same or may be different. b+ is a cation of one or more valences consisting of organic or inorganic substances.
[0034] Each R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an unsaturated cyclic hydrocarbon group, an aromatic group, or a group derived therefrom. In formula (1), n is preferably 1.
[0035] Examples of saturated linear hydrocarbon groups include, but are not limited to, methyl, ethyl, n-propyl, or n-butyl groups. Examples of saturated branched hydrocarbon groups include, but are not limited to, i-propyl or t-butyl groups. Examples of saturated cyclic hydrocarbon groups include, but are not limited to, cyclopentyl or cyclohexyl groups. Examples of unsaturated linear hydrocarbon groups include, but are not limited to, vinyl or allyl groups. Examples of unsaturated branched hydrocarbon groups include, but are not limited to, i-propenyl or 3-butenyl groups. Examples of unsaturated cyclic hydrocarbon groups include, but are not limited to, cyclopentenyl or cyclohexenyl groups. Examples of aromatic groups include, but are not limited to, phenyl or naphthyl groups.
[0036] In addition, the derivative group in R is a carboxy group, a carboxylate group (-COO - ), a functional group in which at least one functional group selected from functional groups such as a hydroxy group, an amino group, and an ammonium group is added or substituted, but is not particularly limited. The number of carbon atoms constituting the main chain of R is not particularly limited, but is preferably 20 or less, more preferably 10 or less. By setting the number of carbon atoms constituting the main chain of R within the above range, the molecular weight of the phosphorus oxoacid group can be set to an appropriate range, which facilitates penetration into the fiber raw material and increases the yield of fibrous cellulose. Note that when there are multiple R in formula (1) or when multiple types of substituents represented by the above formula (1) are introduced into the fibrous cellulose, the multiple Rs present may be the same or different.
[0037] β b+is a monovalent or higher cation made of an organic or inorganic substance. An example of the monovalent or higher cation made of an organic substance is an organic onium ion. An example of the organic onium ion is an organic ammonium ion or an organic phosphonium ion. An example of the organic ammonium ion is an aliphatic ammonium ion or an aromatic ammonium ion, and an example of the organic phosphonium ion is an aliphatic phosphonium ion or an aromatic phosphonium ion. An example of the monovalent or higher cation made of an inorganic substance is an ion of an alkali metal such as sodium, potassium, or lithium, an ion of a divalent metal such as calcium or magnesium, a hydrogen ion, an ammonium ion, or the like. In addition, in formula (1), β b+ When a plurality of substituents represented by the above formula (1) are present or when a plurality of substituents represented by the above formula (1) are introduced into the fibrous cellulose, the plurality of β b+ may be the same or different. The organic or inorganic cations of monovalent or higher are β b+ Sodium or potassium ions are preferred because they are less likely to yellow when the fiber raw material containing the cation is heated and are easy to use industrially, but there is no particular limitation.
[0038] More specifically, examples of the phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group include a phosphoric acid group (-PO3H2), a salt of a phosphoric acid group, a phosphorous acid group (phosphonic acid group) (-PO2H2), and a salt of a phosphorous acid group (phosphonic acid group). In addition, the phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group may be a group in which a phosphoric acid group is condensed (e.g., a pyrophosphate group), a group in which a phosphonic acid is condensed (e.g., a polyphosphonic acid group), a phosphoric ester group (e.g., a monomethyl phosphate group, a polyoxyethylene alkyl phosphate group), an alkyl phosphonic acid group (e.g., a methyl phosphonic acid group), and the like.
[0039] The sulfur oxoacid group (sulfur oxoacid group or a substituent derived from a sulfur oxoacid group) is, for example, a substituent represented by the following formula (2). A plurality of types of substituents represented by the following formula (2) may be introduced into each fibrous cellulose. In this case, the plurality of introduced substituents represented by the following formula (2) may be the same or different.
[0040] [ka]
[0041] In the above structural formula, b and n are natural numbers, p is 0 or 1, and m is an arbitrary number (where 1=b×m). When n is 2 or more, the multiple p's may be the same or different. In the above structural formula, β b+ is a monovalent or higher cation made of an organic or inorganic substance. Examples of the monovalent or higher cation made of an organic substance include organic onium ions. Examples of the organic onium ions include organic ammonium ions and organic phosphonium ions. Examples of the organic ammonium ions include aliphatic ammonium ions and aromatic ammonium ions, and examples of the organic phosphonium ions include aliphatic phosphonium ions and aromatic phosphonium ions. Examples of the monovalent or higher cation made of an inorganic substance include ions of alkali metals such as sodium, potassium, and lithium, ions of divalent metals such as calcium and magnesium, hydrogen ions, and ammonium ions. When multiple types of substituents represented by the above formula (2) are introduced into the fibrous cellulose, the multiple β b+ may be the same or different. The organic or inorganic cations of monovalent or higher are β b+ Sodium or potassium ions are preferred because they are less likely to yellow when the fiber raw material containing the cation is heated and are easy to use industrially, but there is no particular limitation.
[0042] The amount of ionic substituent introduced into fibrous cellulose is, for example, preferably 0.10 mmol / g or more per 1 g (mass) of fibrous cellulose, more preferably 0.20 mmol / g or more, even more preferably 0.40 mmol / g or more, and particularly preferably 0.60 mmol / g or more. The amount of ionic substituent introduced into fibrous cellulose is, for example, preferably 5.20 mmol / g or less per 1 g (mass) of fibrous cellulose, more preferably 3.65 mmol / g or less, even more preferably 3.00 mmol / g or less, even more preferably 2.50 mmol / g or less, even more preferably 2.00 mmol / g or less, even more preferably 1.50 mmol / g or less, and particularly preferably 1.00 mmol / g or less. Here, the denominator in the unit mmol / g is calculated based on the fact that the counter ion of the ionic substituent is a hydrogen ion (H + ) is the mass of the fibrous cellulose. By setting the amount of the ionic substituent introduced within the above range, it is possible to easily refine the fiber raw material and to increase the stability of the fibrous cellulose. As a result, the dust scattering prevention effect of the dust scattering prevention agent can be more effectively improved.
[0043] The amount of ionic substituents introduced into the fibrous cellulose can be measured, for example, by neutralization titration, in which an alkali such as an aqueous sodium hydroxide solution is added to a slurry containing the obtained fibrous cellulose to determine the change in pH, thereby measuring the amount introduced.
[0044] 1 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having phosphorus oxo acid groups and pH. The amount of phosphorus oxo acid groups introduced into the fibrous cellulose is measured, for example, as follows. First, a slurry containing fibrous cellulose is treated with a strongly acidic ion exchange resin. If necessary, the measurement target may be subjected to a defibration treatment similar to the defibration treatment step described below prior to the treatment with the strongly acidic ion exchange resin. Next, the change in pH is observed while adding the aqueous sodium hydroxide solution, and a titration curve such as that shown in the upper part of Figure 1 is obtained. In the titration curve shown in the upper part of Figure 1, the measured pH is plotted against the amount of alkali added, and in the titration curve shown in the lower part of Figure 1, the increment (derivative value) of pH (1 / mmol) against the amount of alkali added is plotted. In this neutralization titration, two points are confirmed in the curve plotting the measured pH against the amount of alkali added, where the increment (derivative value of pH against the amount of alkali added) is maximum. Of these, the first maximum point of the increment obtained after starting to add the alkali is called the first endpoint, and the next maximum point of the increment is called the second endpoint. The amount of alkali required from the start of titration to the first end point is equal to the amount of the first dissociated acid of the fibrous cellulose contained in the slurry used for titration, the amount of alkali required from the first end point to the second end point is equal to the amount of the second dissociated acid of the fibrous cellulose contained in the slurry used for titration, and the amount of alkali required from the start of titration to the second end point is equal to the total amount of dissociated acid of the fibrous cellulose contained in the slurry used for titration. The value obtained by dividing the amount of alkali required from the start of titration to the first end point by the solid content (g) in the slurry to be titrated is the amount of phosphorus oxoacid group introduced (mmol / g). Note that when simply referring to the amount of phosphorus oxoacid group introduced (or the amount of phosphorus oxoacid group), it refers to the amount of the first dissociated acid. In FIG. 1, the region from the start of titration to the first end point is called the first region, and the region from the first end point to the second end point is called the second region. For example, when the phosphorus oxoacid group is a phosphate group and this phosphate group undergoes condensation, the amount of weak acid groups in the phosphorus oxoacid group (also referred to as the second dissociated acid amount in this specification) appears to decrease, and the amount of alkali required in the second region becomes smaller than the amount of alkali required in the first region. On the other hand, the amount of strong acid groups in the phosphorus oxoacid group (also referred to as the first dissociated acid amount in this specification) is equal to the amount of phosphorus atoms regardless of the presence or absence of condensation. In addition, when the phosphorus oxoacid group is a phosphorous acid group, the phosphorus oxoacid group no longer has weak acid groups, so the amount of alkali required in the second region becomes smaller or may become zero. In this case, there is only one point on the titration curve where the pH increment is maximum.
[0045] The above-mentioned amount of phosphorus oxoacid groups introduced (mmol / g) indicates the amount of phosphorus oxoacid groups possessed by the acid-type fibrous cellulose (hereinafter referred to as the amount of phosphorus oxoacid groups (acid type)), since the denominator indicates the mass of the acid-type fibrous cellulose. On the other hand, when the counter ion of the phosphorus oxoacid group is replaced with an arbitrary cation C so as to be the charge equivalent, the amount of phosphorus oxoacid groups possessed by the fibrous cellulose in which the cation C is the counter ion (hereinafter referred to as the amount of phosphorus oxoacid groups (C type)) can be obtained by converting the denominator to the mass of the fibrous cellulose when the cation C is the counter ion. That is, it is calculated according to the following formula. Amount of phosphorus oxoacid group (C type) = Amount of phosphorus oxoacid group (acid type) / {1+(W-1)×A / 1000} A [mmol / g]: total amount of anions derived from phosphorus oxoacid groups in fibrous cellulose (total amount of dissociated acid from phosphorus oxoacid groups) W: Formula weight per valence of cation C (for example, Na is 23, Al is 9)
[0046] 2 is a graph showing the relationship between the amount of NaOH dropped onto a dispersion containing fibrous cellulose having a carboxy group as an ionic substituent and the pH. The amount of carboxy group introduced into the fibrous cellulose is measured, for example, as follows. First, a dispersion liquid containing fibrous cellulose is treated with a strongly acidic ion exchange resin. If necessary, a defibration treatment similar to the defibration treatment step described below may be performed on the measurement target prior to the treatment with the strongly acidic ion exchange resin. Next, the change in pH is observed while adding the aqueous sodium hydroxide solution, and a titration curve as shown in the upper part of FIG. 2 is obtained. In the titration curve shown in the upper part of FIG. 2, the measured pH is plotted against the amount of added alkali, and in the titration curve shown in the lower part of FIG. 2, the increment (differential value) (1 / mmol) of pH against the amount of added alkali is plotted. In this neutralization titration, one point where the increment (differential value of pH against the amount of added alkali) is maximum is confirmed in the curve plotting the measured pH against the amount of added alkali, and this maximum point is called the first end point. Here, the region from the start of titration to the first end point in FIG. 2 is called the first region. The amount of alkali required in the first region is equal to the amount of carboxyl groups in the dispersion used for titration. The amount of alkali required in the first region of the titration curve (mmol) is divided by the solid content (g) in the dispersion containing the fibrous cellulose to be titrated to calculate the amount of carboxyl groups introduced (mmol / g).
[0047] The above-mentioned amount of carboxyl groups introduced (mmol / g) indicates the amount of carboxyl groups in the acid-type fibrous cellulose (hereinafter referred to as the amount of carboxyl groups (acid type)) since the denominator is the mass of the acid-type fibrous cellulose. On the other hand, when the counter ion of the carboxyl group is replaced with any cation C so as to be the charge equivalent, the amount of carboxyl groups in the fibrous cellulose in which the cation C is the counter ion (hereinafter referred to as the amount of carboxyl groups (C type)) can be obtained by converting the denominator to the mass of the fibrous cellulose when the cation C is the counter ion. That is, it is calculated by the following formula. Carboxylic acid amount (C type) = Carboxylic acid amount (acid type) / {1 + (W-1) x (Carboxylic acid amount (acid type)) / 1000} W: Formula weight per valence of cation C (for example, Na is 23, Al is 9)
[0048] In measuring the amount of ionic substituents by titration, if the amount of sodium hydroxide solution dropped is too large or the titration interval is too short, the amount of ionic substituents may be lower than the actual amount, and an accurate value may not be obtained. As an appropriate amount of drop and titration interval, for example, it is preferable to titrate 10 to 50 μL of 0.1N sodium hydroxide solution every 5 to 30 seconds. In addition, in order to eliminate the influence of carbon dioxide dissolved in the fibrous cellulose-containing slurry, it is preferable to measure while blowing an inert gas such as nitrogen gas into the slurry from 15 minutes before the start of titration until the end of titration.
[0049] The amount of sulfur oxoacid groups or sulfone groups introduced into fibrous cellulose can be calculated by freeze-drying a slurry containing fibrous cellulose, pulverizing the slurry, and measuring the amount of sulfur in the resulting pulverized sample. Specifically, the slurry containing fibrous cellulose is freeze-dried, and the resulting pulverized sample is subjected to pressurized heating decomposition with nitric acid in a closed container, and then appropriately diluted and the amount of sulfur is measured by ICP-OES. The value calculated by dividing the value by the bone dry mass of the fibrous cellulose used is taken as the amount of sulfur oxoacid groups or sulfone groups (unit: mmol / g) of the fibrous cellulose.
[0050] In order to obtain fine fibrous cellulose having an ionic substituent introduced thereinto, it is preferable to have an ionic substituent introduction step for introducing an ionic substituent into a fiber raw material containing cellulose, a washing step, an alkali treatment step (neutralization step), and a defibration treatment step in this order, and an acid treatment step may be included instead of or in addition to the washing step. Examples of the ionic substituent introduction step include a phosphorus oxo acid group introduction step, a carboxy group introduction step, a sulfur oxo acid group introduction step, a xanthate group introduction step, a phosphonic or phosphine group introduction step, a sulfonic group introduction step, and a cationic group introduction step. Each of these steps will be described below.
[0051] (Method of producing fine fibrous cellulose) <Textile raw materials> Fine fibrous cellulose is produced from a fiber raw material containing cellulose. The fiber raw material containing cellulose is not particularly limited, but it is preferable to use pulp because it is easily available and inexpensive. Examples of pulp include wood pulp, non-wood pulp, and deinked pulp. Examples of wood pulp include, but are not particularly limited to, chemical pulp such as hardwood kraft pulp (LBKP), softwood kraft pulp (NBKP), sulfite pulp (SP), dissolving pulp (DP), soda pulp (AP), unbleached kraft pulp (UKP) and oxygen bleached kraft pulp (OKP), semi-chemical pulp such as semi-chemical pulp (SCP) and chemi-ground wood pulp (CGP), mechanical pulp such as groundwood pulp (GP) and thermomechanical pulp (TMP, BCTMP), etc. Examples of non-wood pulp include, but are not particularly limited to, cotton-based pulp such as cotton linters and cotton lint, and non-wood-based pulp such as hemp, wheat straw, and bagasse. The deinked pulp is not particularly limited, and may be deinked pulp made from waste paper. The pulp of this embodiment may be one of the above, or a mixture of two or more. Among the above pulps, wood pulp and deinked pulp are preferable from the viewpoint of availability. Among wood pulps, chemical pulp is more preferable, and kraft pulp and sulfite pulp are even more preferable, from the viewpoint of a high cellulose ratio and a high yield of fine fibrous cellulose during defibration treatment, and of small decomposition of cellulose in the pulp and of obtaining long-fiber fine fibrous cellulose with a large axial ratio.
[0052] As a fiber raw material containing cellulose, for example, cellulose contained in sea squirts and bacterial cellulose produced by acetic acid bacteria can be used. Also, instead of a fiber raw material containing cellulose, a fiber formed by a linear nitrogen-containing polysaccharide polymer such as chitin or chitosan can be used.
[0053] <Phosphorus oxo acid group introduction step> The process for producing fine fibrous cellulose preferably includes, for example, a phosphorus oxoacid group introduction step as an ionic substituent introduction step. The phosphorus oxoacid group introduction step is a step of reacting at least one compound (hereinafter also referred to as "compound A") selected from compounds capable of introducing phosphorus oxoacid groups by reacting with hydroxyl groups possessed by a fiber raw material containing cellulose with the fiber raw material containing cellulose. This step results in the production of fibers into which phosphorus oxoacid groups have been introduced.
[0054] In the phosphorus oxoacid group introduction step according to this embodiment, the reaction of the cellulose-containing fiber raw material with compound A may be carried out in the presence of at least one selected from urea and its derivatives (hereinafter also referred to as "compound B"). Alternatively, the reaction of the cellulose-containing fiber raw material with compound A may be carried out in the absence of compound B.
[0055] An example of a method for acting compound A on a fiber raw material in the presence of compound B includes a method of mixing compound A and compound B with a fiber raw material in a dry state, a wet state, or a slurry state. Of these, it is preferable to use a fiber raw material in a dry state or a wet state, and it is particularly preferable to use a fiber raw material in a dry state, because the reaction is highly uniform. The form of the fiber raw material is not particularly limited, but it is preferable to use a cotton-like or thin sheet-like form. Compound A and compound B can be added to the fiber raw material in a powder form, a solution form dissolved in a solvent, or a melted state by heating to a melting point or higher. Of these, it is preferable to add them in a solution form dissolved in a solvent, especially in an aqueous solution form, because the reaction is highly uniform. Compound A and compound B may be added to the fiber raw material simultaneously, separately, or as a mixture. The method of adding compound A and compound B is not particularly limited, but when compound A and compound B are in a solution form, the fiber raw material may be immersed in the solution to absorb the liquid and then removed, or the solution may be dropped onto the fiber raw material. In addition, the required amounts of compound A and compound B may be added to the fiber raw material, or excess amounts of compound A and compound B may be added to the fiber raw material, respectively, and then the excess compound A and compound B may be removed by squeezing or filtration.
[0056] The compound A used in this embodiment may be any compound that has a phosphorus atom and can form an ester bond with cellulose, and may include, but is not limited to, phosphoric acid or a salt thereof, phosphorous acid or a salt thereof, dehydrated condensed phosphoric acid or a salt thereof, and anhydrous phosphoric acid (diphosphorus pentoxide). Phosphoric acid may be used with various purities, for example, 100% phosphoric acid (orthophosphoric acid) or 85% phosphoric acid. Phosphorous acid may be 99% phosphorous acid (phosphonic acid). Dehydrated condensed phosphoric acid is a phosphoric acid in which two or more molecules are condensed by a dehydration reaction, and examples of the phosphoric acid include pyrophosphoric acid and polyphosphoric acid. Phosphates, phosphites, and dehydrated condensed phosphates include lithium salts, sodium salts, potassium salts, and ammonium salts of phosphoric acid, phosphorous acid, or dehydrated condensed phosphoric acid, and these may be neutralized to various degrees. Among these, from the viewpoints of high efficiency of introduction of phosphate groups, easier improvement of defibration efficiency in the defibration step described below, low cost, and ease of industrial application, phosphoric acid, sodium salt of phosphoric acid, potassium salt of phosphoric acid, ammonium salt of phosphoric acid, or phosphorous acid, sodium salt of phosphorous acid, potassium salt of phosphorous acid, or ammonium salt of phosphorous acid are preferred, and phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, or phosphorous acid and sodium phosphite are more preferred.
[0057] The amount of compound A added to the fiber raw material is not particularly limited, but for example, when the amount of compound A added is converted into the amount of phosphorus atoms, the amount of phosphorus atoms added to the fiber raw material (bone dry mass) is preferably 0.5% by mass or more and 100% by mass or less, more preferably 1% by mass or more and 50% by mass or less, and even more preferably 2% by mass or more and 30% by mass or less. By setting the amount of phosphorus atoms added to the fiber raw material within the above range, the yield of fine fibrous cellulose can be further improved. On the other hand, by setting the amount of phosphorus atoms added to the fiber raw material to the above upper limit or less, a balance between the effect of improving the yield and the cost can be achieved.
[0058] The compound B used in this embodiment is at least one selected from urea and its derivatives as described above. Examples of compound B include urea, biuret, 1-phenylurea, 1-benzylurea, 1-methylurea, and 1-ethylurea. From the viewpoint of improving the uniformity of the reaction, it is preferable to use compound B as an aqueous solution. In addition, from the viewpoint of further improving the uniformity of the reaction, it is preferable to use an aqueous solution in which both compound A and compound B are dissolved.
[0059] The amount of compound B added relative to the fiber raw material (bone dry mass) is not particularly limited, but is preferably, for example, 1 mass% or more and 500 mass% or less, more preferably 10 mass% or more and 400 mass% or less, and even more preferably 100 mass% or more and 350 mass% or less.
[0060] In the reaction of a fiber raw material containing cellulose with compound A, in addition to compound B, for example, amides or amines may be included in the reaction system. Examples of amides include formamide, dimethylformamide, acetamide, and dimethylacetamide. Examples of amines include methylamine, ethylamine, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, pyridine, ethylenediamine, and hexamethylenediamine. Among these, triethylamine in particular is known to act as a good reaction catalyst.
[0061] In the phosphorus oxo acid group introduction step, it is preferable to add or mix the compound A or the like to the fiber raw material, and then heat-treat the fiber raw material. It is preferable to select a temperature for the heat treatment that can efficiently introduce the phosphorus oxo acid group while suppressing thermal decomposition and hydrolysis of the fiber. The heat treatment temperature is, for example, preferably 50°C to 300°C, more preferably 100°C to 250°C, and even more preferably 130°C to 200°C. In addition, for the heat treatment, equipment having various heat media can be used, such as a stirring dryer, a rotary dryer, a disk dryer, a roll-type heater, a plate-type heater, a fluidized bed dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far-infrared heater, or a microwave heater.
[0062] In the heat treatment according to the present embodiment, for example, a method of adding compound A to a thin sheet-like fiber raw material by a method such as impregnation, followed by heating, or a method of heating while kneading or stirring the fiber raw material and compound A in a kneader or the like, can be adopted. This makes it possible to suppress unevenness in the concentration of compound A in the fiber raw material and introduce phosphorus oxo acid groups more uniformly onto the surface of the cellulose contained in the fiber raw material. This is believed to be due to the fact that when water molecules move to the surface of the fiber raw material as it dries, the dissolved compound A can be prevented from being attracted to the water molecules by surface tension and moving to the surface of the fiber raw material in the same manner (i.e., causing unevenness in the concentration of compound A).
[0063] In addition, the heating device used in the heat treatment is preferably a device that can constantly discharge, for example, the moisture held by the slurry and the moisture generated in the dehydration condensation (phosphorylation) reaction between compound A and hydroxyl groups contained in cellulose or the like in the fiber raw material, outside the device system. Examples of such heating devices include ovens that use a blowing system. By constantly discharging the moisture within the device system, it is possible to suppress the hydrolysis reaction of phosphate ester bonds, which is the reverse reaction of phosphate esterification, and also to suppress acid hydrolysis of the sugar chains in the fibers. This makes it possible to obtain fine fibrous cellulose with a high axial ratio.
[0064] The time for the heat treatment is, for example, preferably from 1 second to 300 minutes after the moisture is substantially removed from the fiber raw material, more preferably from 1 second to 1000 seconds, and even more preferably from 10 seconds to 800 seconds. In this embodiment, the introduction amount of phosphorus oxo acid groups can be kept within a preferred range by setting the heating temperature and heating time within appropriate ranges.
[0065] The phosphorus oxo acid group introduction step may be carried out at least once, but may also be repeated two or more times. By carrying out the phosphorus oxo acid group introduction step two or more times, a large number of phosphorus oxo acid groups can be introduced into the fiber raw material. In the present embodiment, a preferred embodiment includes carrying out the phosphorus oxo acid group introduction step two times.
[0066] The amount of phosphorus oxoacid groups introduced into the fiber raw material is, for example, preferably 0.10 mmol / g or more per 1 g (mass) of fiber raw material, more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 1.00 mmol / g or more. The amount of phosphorus oxoacid groups introduced into the fiber raw material is, for example, preferably 5.20 mmol / g or less per 1 g (mass) of fiber raw material, more preferably 3.65 mmol / g or less, and even more preferably 3.00 mmol / g or less. By setting the amount of phosphorus oxoacid groups introduced within the above range, it is possible to easily micronize the fiber raw material and to increase the stability of the fine fibrous cellulose.
[0067] <Carboxy group introduction step> The process for producing fine fibrous cellulose may include, for example, a carboxyl group introduction step as an ionic substituent introduction step. The carboxyl group introduction step is carried out by subjecting a fiber raw material containing cellulose to an oxidation treatment such as ozone oxidation, oxidation by the Fenton method, or TEMPO oxidation treatment, or treating the raw material with a compound having a carboxylic acid-derived group or a derivative thereof, or an acid anhydride of a compound having a carboxylic acid-derived group or a derivative thereof.
[0068] Examples of compounds having a group derived from a carboxylic acid include, but are not limited to, dicarboxylic acid compounds such as maleic acid, succinic acid, phthalic acid, fumaric acid, glutaric acid, adipic acid, and itaconic acid, and tricarboxylic acid compounds such as citric acid and aconitic acid. Examples of derivatives of compounds having a group derived from a carboxylic acid include, but are not limited to, imidized products of acid anhydrides of compounds having a carboxy group, and derivatives of acid anhydrides of compounds having a carboxy group. Examples of imidized products of acid anhydrides of compounds having a carboxy group include, but are not limited to, imidized products of dicarboxylic acid compounds such as maleimide, succinimide, and phthalimide.
[0069] The acid anhydride of a compound having a group derived from a carboxylic acid is not particularly limited, but examples thereof include acid anhydrides of dicarboxylic acid compounds such as maleic anhydride, succinic anhydride, phthalic anhydride, glutaric anhydride, adipic anhydride, itaconic anhydride, etc. Furthermore, the derivative of an acid anhydride of a compound having a group derived from a carboxylic acid is not particularly limited, but examples thereof include acid anhydrides of compounds having a carboxy group such as dimethylmaleic anhydride, diethylmaleic anhydride, diphenylmaleic anhydride, etc., in which at least a part of the hydrogen atoms is substituted with a substituent such as an alkyl group or a phenyl group.
[0070] When a TEMPO oxidation treatment is performed in the carboxyl group introduction step, it is preferable to perform the treatment under conditions of pH 6 or more and 8 or less. Such a treatment is also called a neutral TEMPO oxidation treatment. The neutral TEMPO oxidation treatment can be performed, for example, by adding pulp as a fiber raw material, a nitroxy radical such as TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl) as a catalyst, and sodium hypochlorite as a sacrificial reagent to a sodium phosphate buffer solution (pH = 6.8). By further allowing sodium chlorite to coexist, aldehydes generated during the oxidation process can be efficiently oxidized to carboxyl groups. The TEMPO oxidation treatment may also be performed under conditions of pH 10 or more and 11 or less. Such a treatment is also called an alkaline TEMPO oxidation treatment. The alkaline TEMPO oxidation treatment can be performed, for example, by adding a nitroxy radical such as TEMPO as a catalyst, sodium bromide as a cocatalyst, and sodium hypochlorite as an oxidizing agent to pulp as a fiber raw material.
[0071] The amount of carboxyl groups introduced into the fiber raw material varies depending on the type of the substituent, but for example, when the carboxyl groups are introduced by TEMPO oxidation, it is preferably 0.10 mmol / g or more per 1 g (mass) of the fiber raw material, more preferably 0.20 mmol / g or more, even more preferably 0.40 mmol / g or more, and particularly preferably 0.60 mmol / g or more. The amount of carboxyl groups introduced into the fibrous cellulose is preferably 3.65 mmol / g or less, more preferably 3.00 mmol / g or less, even more preferably 2.50 mmol / g or less, even more preferably 2.00 mmol / g or less, even more preferably 1.50 mmol / g or less, and particularly preferably 1.00 mmol / g or less. In addition, when the substituent is a carboxymethyl group, the amount of carboxyl groups introduced may be 5.8 mmol / g or less per 1 g (mass) of fine fibrous cellulose. By setting the amount of carboxyl groups introduced within the above range, it is possible to easily fine the fiber raw material and to increase the stability of the fibrous cellulose.
[0072] <Sulfur oxoacid group introduction step> The process for producing fine fibrous cellulose may include, for example, a sulfur oxoacid group introduction step as an ionic substituent introduction step, in which a hydroxyl group in a fiber raw material containing cellulose reacts with a sulfur oxoacid to obtain cellulose fibers having sulfur oxoacid groups (sulfur oxoacid group-introduced fibers).
[0073] In the sulfur oxo acid group introduction step, instead of compound A in the above-mentioned <phosphorus oxo acid group introduction step>, at least one compound (hereinafter also referred to as "compound C") selected from compounds capable of introducing sulfur oxo acid groups by reacting with hydroxyl groups of fiber raw materials containing cellulose is used. Compound C may be any compound having a sulfur atom and capable of forming an ester bond with cellulose, and may include, but is not limited to, sulfuric acid or a salt thereof, sulfurous acid or a salt thereof, and sulfuric acid amide. As sulfuric acid, sulfuric acid of various purities may be used, for example, 96% sulfuric acid (concentrated sulfuric acid). As sulfurous acid, 5% sulfurous acid water may be used. As sulfates or sulfites, lithium salts, sodium salts, potassium salts, ammonium salts of sulfates or sulfites may be used, and these may have various degrees of neutralization. As sulfuric acid amides, sulfamic acid or the like may be used. In the sulfur oxo acid group introduction step, it is preferable to use compound B in the above-mentioned <phosphorus oxo acid group introduction step> in the same manner.
[0074] In the sulfur oxoacid group introduction step, it is preferable to mix the cellulose raw material with an aqueous solution containing sulfur oxoacid and urea and / or a urea derivative, and then heat-treat the cellulose raw material. It is preferable to select a heat-treatment temperature that allows efficient introduction of sulfur oxoacid groups while suppressing thermal decomposition and hydrolysis of the fibers. The heat-treatment temperature is preferably 100°C or higher, more preferably 120°C or higher, and even more preferably 150°C or higher. The heat-treatment temperature is preferably 300°C or lower, more preferably 250°C or lower, and even more preferably 200°C or lower.
[0075] In the heat treatment step, it is preferable to heat until substantially no moisture is present. For this reason, the heat treatment time varies depending on the amount of moisture contained in the cellulose raw material and the amount of the aqueous solution containing sulfur oxoacid and urea and / or a urea derivative added, but is preferably, for example, 10 seconds or more and 10,000 seconds or less. For the heat treatment, equipment having various heat media can be used, such as a stirring dryer, a rotary dryer, a disk dryer, a roll type heater, a plate type heater, a fluidized bed dryer, a band type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far infrared heater, a microwave heater, and a high frequency dryer.
[0076] The amount of sulfur oxoacid groups introduced into the cellulose raw material is preferably 0.50 mmol / g or more, more preferably 0.70 mmol / g or more, and even more preferably 1.00 mmol / g or more. The amount of sulfur oxoacid groups introduced into the cellulose raw material is preferably 5.00 mmol / g or less, and more preferably 3.00 mmol / g or less. By setting the amount of sulfur oxoacid groups introduced within the above range, it is possible to easily refine the fiber raw material and to increase the stability of the fibrous cellulose.
[0077] <Oxidation step using a chlorine-based oxidizing agent (second carboxyl group introduction step)> The ionic substituent introduction step may include an oxidation step using a chlorine-based oxidizing agent, in which the chlorine-based oxidizing agent is added to a wet or dry fiber raw material having a hydroxyl group to cause a reaction, thereby introducing a carboxyl group into the fiber raw material.
[0078] Examples of chlorine-based oxidizing agents include hypochlorous acid, hypochlorites, chlorous acid, chlorites, chloric acid, chlorates, perchloric acid, perchlorates, and chlorine dioxide. In terms of the efficiency of introducing a substituent, and therefore the efficiency of defibration, cost, and ease of handling, the chlorine-based oxidizing agent is preferably sodium hypochlorite, sodium chlorite, or chlorine dioxide. When adding a chlorine-based oxidizing agent, it may be added to the fiber raw material as it is as a reagent (solid or liquid), or it may be added after dissolving in an appropriate solvent.
[0079] The concentration of the chlorine-based oxidizing agent in the solution in the oxidation step using the chlorine-based oxidizing agent is, for example, preferably 1% by mass to 1,000% by mass, more preferably 5% by mass to 500% by mass, and even more preferably 10% by mass to 100% by mass. The amount of the chlorine-based oxidizing agent added per 100 parts by mass of the fiber raw material is preferably 1 part by mass to 100,000 parts by mass, more preferably 10 parts by mass to 10,000 parts by mass, and even more preferably 100 parts by mass to 5,000 parts by mass.
[0080] The reaction time with the chlorine-based oxidizing agent in the oxidation step using the chlorine-based oxidizing agent may vary depending on the reaction temperature, but is preferably from 1 minute to 1,000 minutes, more preferably from 10 minutes to 500 minutes, and even more preferably from 20 minutes to 400 minutes. The pH during the reaction is preferably from 5 to 15, more preferably from 7 to 14, and even more preferably from 9 to 13. At the start of the reaction, the pH during the reaction is preferably kept constant (for example, pH 11) by appropriately adding hydrochloric acid or sodium hydroxide. After the reaction, excess reaction reagents, by-products, etc. may be washed with water and removed by filtration or the like.
[0081] <Xanthate group introduction step (xanthogen acid esterification step)> The ionic substituent introduction step may include, for example, a xanthate group introduction step (hereinafter also referred to as a xanthate formation step). In the xanthate formation step, carbon disulfide and an alkali compound are added to a wet or dry fiber raw material having a hydroxyl group to react with each other, thereby introducing a xanthate group into the fiber raw material. Specifically, carbon disulfide is added to a fiber raw material that has been converted into alkali cellulose by the method described below, and the reaction is carried out.
[0082] <<Alkaline cellulose>> When introducing an ionic substituent into a fiber raw material, it is preferable to make the cellulose contained in the fiber raw material into an alkali cellulose by applying an alkali solution to the cellulose. This treatment causes some of the hydroxyl groups of the cellulose to be ionized, thereby increasing the nucleophilicity (reactivity). The alkali compound contained in the alkali solution is not particularly limited, and may be an inorganic alkali compound or an organic alkali compound. For example, sodium hydroxide, potassium hydroxide, tetraethylammonium hydroxide, and tetrabutylammonium hydroxide are preferably used because of their high versatility. The alkali cellulose may be made into an alkali cellulose simultaneously with the introduction of an ionic substituent, before the introduction, or at both the same timing.
[0083] The solution temperature at the start of alkali cellulose formation is preferably 0°C or higher and 50°C or lower, more preferably 5°C or higher and 40°C or lower, and even more preferably 10°C or higher and 30°C or lower.
[0084] The alkali concentration in the alkali solution is preferably 0.01 mol / L to 4 mol / L in terms of molar concentration, more preferably 0.1 mol / L to 3 mol / L inclusive, and even more preferably 1 mol / L to 2.5 mol / L inclusive. In particular, when the treatment temperature in the alkali cellulose formation is less than 10° C., the alkali concentration is preferably 1 mol / L to 2 mol / L inclusive.
[0085] The treatment time for alkali cellulose formation is preferably 1 minute or more, more preferably 10 minutes or more, and even more preferably 30 minutes or more, and the alkali treatment time is preferably 6 hours or less, more preferably 5 hours or less, and even more preferably 4 hours or less.
[0086] By adjusting the type of alkaline solution, treatment temperature, concentration, and immersion time as described above, it is possible to suppress the penetration of the alkaline solution into the crystalline regions of cellulose, making it easier to maintain the crystal structure of cellulose type I, and increasing the yield of fine fibrous cellulose.
[0087] When the introduction of ionic substituents and the conversion to alkali cellulose are not carried out simultaneously, the conversion to alkali cellulose is preferably carried out before the introduction of ionic substituents. In this case, the alkali cellulose obtained by the conversion to alkali cellulose is preferably subjected to solid-liquid separation and water removal by a general deliquation method such as centrifugation or filtration. This improves the reaction efficiency in the subsequent ionic substituent introduction step. The cellulose fiber concentration after solid-liquid separation is preferably 5% to 50%, more preferably 10% to 40%, and even more preferably 15% to 35%.
[0088] <Phosphonic or Phosphine Group Introduction Step (Phosphoalkylation Step)> The ionic substituent introduction step may include a phosphonic or phosphine group introduction step (phosphoalkylation step). In the phosphoalkylation step, a compound having a reactive group and a phosphonic or phosphine group (compound E A ), an optional alkaline compound, and compound B selected from the above-mentioned urea and its derivatives are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a phosphonic or phosphine group into the fiber raw material.
[0089] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group). Compound E A Examples of the compound include vinyl phosphonic acid, phenyl vinyl phosphonic acid, and phenyl vinyl phosphinic acid. From the viewpoints of the efficiency of introducing the substituent, the defibration efficiency, the cost, and the ease of handling, compound E A is preferably vinylphosphonic acid. Furthermore, as an optional component, it is also preferable to use compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner, and the amount added is also preferably as described above.
[0090] Compound E A When adding, it may be added to the fiber raw material as a reagent (solid or liquid) as it is, or may be dissolved in a suitable solvent and added. It is preferable that the fiber raw material is converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0091] The temperature during the reaction is, for example, preferably from 50°C to 300°C, more preferably from 100°C to 250°C, and even more preferably from 130°C to 200°C.
[0092] Compound E A The amount of addition per 100 parts by mass of the fiber raw material is preferably 1 part by mass or more and 100,000 parts by mass or less, more preferably 2 parts by mass or more and 10,000 parts by mass or less, and even more preferably 5 parts by mass or more and 1,000 parts by mass or less.
[0093] The reaction time may vary depending on the reaction temperature, but is preferably, for example, from 1 minute to 1,000 minutes, more preferably from 10 minutes to 500 minutes, and even more preferably from 20 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0094] <Sulfone Group Introduction Step (Sulfoalkylation Step) (Second Sulfone Group Introduction Step)> The ionic substituent introduction step may include a sulfone group introduction step (sulfoalkylation step). In the sulfoalkylation, a compound having a reactive group and a sulfone group (compound E) is used as an essential component. B ) and, as an optional component, an alkaline compound, and compound B selected from the above-mentioned urea and its derivatives are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a sulfone group into the fiber raw material.
[0095] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group). Compound E B Examples of suitable sulfonates include sodium 2-chloroethanesulfonate, sodium vinylsulfonate, sodium p-styrenesulfonate, and 2-acrylamido-2-methylpropanesulfonic acid. Among these, compound E is particularly preferred in terms of the efficiency of introducing substituents, and therefore the defibration efficiency, cost, and ease of handling. B is preferably sodium vinyl sulfonate. Furthermore, as an optional component, it is also preferable to use compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner, and the amount added is also preferably as described above.
[0096] Compound E B When adding, it may be added to the fiber raw material as a reagent (solid or liquid) as it is, or may be dissolved in a suitable solvent and added. It is preferable that the fiber raw material is converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0097] The temperature during the reaction is, for example, preferably from 50°C to 300°C, more preferably from 100°C to 250°C, and even more preferably from 130°C to 200°C.
[0098] Compound E BThe amount of addition per 100 parts by mass of the fiber raw material is preferably 1 part by mass or more and 100,000 parts by mass or less, more preferably 2 parts by mass or more and 10,000 parts by mass or less, and even more preferably 5 parts by mass or more and 1,000 parts by mass or less.
[0099] The reaction time may vary depending on the reaction temperature, but is preferably, for example, from 1 minute to 1,000 minutes, more preferably from 10 minutes to 500 minutes, and even more preferably from 15 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0100] <Carboxyalkylation step (third carboxy group introduction step)> The ionic substituent introduction step may include a carboxyalkylation step. As an essential component, a compound having a reactive group and a carboxy group (compound E C ), an optional alkaline compound, and compound B selected from the above-mentioned urea and its derivatives are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a carboxyl group into the fiber raw material.
[0101] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group). Compound E C As the chloropropionic acid, monochloroacetic acid, sodium monochloroacetate, 2-chloropropionic acid, 3-chloropropionic acid, sodium 2-chloropropionate, and sodium 3-chloropropionate are preferred from the standpoint of efficiency of introducing substituents, and therefore defibration efficiency, cost, and ease of handling. Furthermore, as an optional component, it is also preferable to use compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner, and the amount added is also preferably as described above.
[0102] Compound E CWhen adding, it may be added to the fiber raw material as a reagent (solid or liquid) as it is, or may be dissolved in a suitable solvent and added. It is preferable that the fiber raw material is converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0103] The temperature during the reaction is, for example, preferably from 50°C to 300°C, more preferably from 100°C to 250°C, and even more preferably from 130°C to 200°C.
[0104] Compound E C The amount of addition per 100 parts by mass of the fiber raw material is preferably 1 part by mass or more and 100,000 parts by mass or less, more preferably 2 parts by mass or more and 10,000 parts by mass or less, and even more preferably 5 parts by mass or more and 1,000 parts by mass or less.
[0105] The reaction time may vary depending on the reaction temperature, but is preferably, for example, from 1 minute to 1,000 minutes, more preferably from 3 minutes to 500 minutes, and even more preferably from 5 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0106] <Cationic group introduction step (cationization step)> As an essential component, a compound having a reactive group and a cationic group (compound E D ), an optional alkaline compound, and compound B selected from the above-mentioned urea and its derivatives are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a cationic group into the fiber raw material.
[0107] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group). Examples of the cationic group include an ammonium group, a phosphonium group, a sulfonium group, etc. Among these, the cationic group is preferably an ammonium group. Compound E D As the alkyl group, glycidyl trimethyl ammonium chloride, 3-chloro-2-hydroxypropyl trimethyl ammonium chloride, etc. are preferred from the viewpoints of the efficiency of introducing a substituent, and therefore the defibration efficiency, cost, and ease of handling. Furthermore, as an optional component, it is also preferable to use the compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner. The amount of addition is also preferably as described above.
[0108] Compound E D When adding, it may be added to the fiber raw material as a reagent (solid or liquid) as it is, or may be dissolved in a suitable solvent and added. It is preferable that the fiber raw material is converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0109] The temperature during the reaction is, for example, preferably from 50°C to 300°C, more preferably from 100°C to 250°C, and even more preferably from 130°C to 200°C.
[0110] Compound E D The amount of addition per 100 parts by mass of the fiber raw material is preferably 1 part by mass or more and 100,000 parts by mass or less, more preferably 2 parts by mass or more and 10,000 parts by mass or less, and even more preferably 5 parts by mass or more and 1,000 parts by mass or less.
[0111] The reaction time may vary depending on the reaction temperature, but is preferably from 1 minute to 1,000 minutes, more preferably from 5 minutes to 500 minutes, and even more preferably from 10 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0112] <Cleaning process> In the method for producing fine fibrous cellulose in this embodiment, a washing step can be carried out on the ionic substituent-introduced fiber as necessary. The washing step is carried out, for example, by washing the ionic substituent-introduced fiber with water or an organic solvent. The washing step may be carried out after each step described below, and the number of washing steps carried out in each washing step is not particularly limited.
[0113] <Alkaline treatment process> When producing fine fibrous cellulose, an alkali treatment may be carried out on the fiber raw material between the step of introducing an ionic substituent and the step of defibrating the fiber, which will be described later. The method of the alkali treatment is not particularly limited, but may be, for example, a method of immersing the fiber having an ionic substituent introduced therein in an alkali solution.
[0114] The alkaline compound contained in the alkaline solution is not particularly limited, and may be an inorganic alkaline compound or an organic alkaline compound. In this embodiment, it is preferable to use, for example, sodium hydroxide or potassium hydroxide as the alkaline compound because of its high versatility. The solvent contained in the alkaline solution may be either water or an organic solvent. Among them, the solvent contained in the alkaline solution is preferably a polar solvent including water or a polar organic solvent exemplified by alcohol, and more preferably an aqueous solvent including at least water. As the alkaline solution, for example, an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution is preferable because of its high versatility.
[0115] The temperature of the alkaline solution in the alkaline treatment step is not particularly limited, but is preferably, for example, from 5° C. to 80° C., and more preferably from 10° C. to 60° C. The immersion time of the ionic substituent-introduced fiber in the alkaline solution in the alkaline treatment step is not particularly limited, but is, for example, preferably from 5 minutes to 30 minutes, and more preferably from 10 minutes to 20 minutes. The amount of the alkaline solution used in the alkaline treatment is not particularly limited, but is, for example, preferably from 100 mass% to 100,000 mass%, and more preferably from 1,000 mass% to 10,000 mass%, based on the absolute dry mass of the ionic substituent-introduced fiber.
[0116] In order to reduce the amount of alkaline solution used in the alkaline treatment step, the ionic substituent-introduced fiber may be washed with water or an organic solvent after the ionic substituent-introducing step and before the alkaline treatment step. From the viewpoint of improving handleability, it is preferable to wash the alkaline-treated ionic substituent-introduced fiber with water or an organic solvent after the alkaline treatment step and before the defibration treatment step.
[0117] <Acid treatment process> When producing fine fibrous cellulose, the fiber raw material may be subjected to an acid treatment between the step of introducing an ionic substituent and the defibration treatment step described later. For example, the step of introducing an ionic substituent, the acid treatment, the alkali treatment, and the defibration treatment may be performed in this order.
[0118] The method of acid treatment is not particularly limited, but may be, for example, a method of immersing the fiber raw material in an acidic solution containing an acid. The concentration of the acidic solution used is not particularly limited, but is preferably, for example, 10% by mass or less, and more preferably, 5% by mass or less. The pH of the acidic solution used is not particularly limited, but is preferably, for example, 0 to 4, and more preferably, 1 to 3. The acid contained in the acidic solution may be, for example, an inorganic acid, a sulfonic acid, a carboxylic acid, or the like. Examples of inorganic acids include sulfuric acid, nitric acid, hydrobromic acid, hydroiodic acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, phosphoric acid, and boric acid. Examples of sulfonic acids include, for example, methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid. Examples of carboxylic acids include, for example, formic acid, acetic acid, citric acid, gluconic acid, lactic acid, oxalic acid, and tartaric acid. Among these, it is particularly preferable to use hydrochloric acid or sulfuric acid.
[0119] The temperature of the acid solution in the acid treatment is not particularly limited, but is preferably, for example, from 5° C. to 100° C., and more preferably from 20° C. to 90° C. The immersion time in the acid solution in the acid treatment is not particularly limited, but is, for example, preferably from 5 minutes to 120 minutes, and more preferably from 10 minutes to 60 minutes. The amount of the acid solution used in the acid treatment is not particularly limited, but is, for example, preferably from 100 mass% to 100,000 mass%, and more preferably from 1,000 mass% to 10,000 mass%, based on the absolute dry mass of the fiber raw material.
[0120] <Defibrillation processing> The ionic substituent-introduced fibers are defibrated in a defibration process to obtain fine fibrous cellulose. In the defibration process, for example, a defibration treatment device can be used. The defibration treatment device is not particularly limited, but for example, a high-speed defibrator, a grinder (stone mill type grinder), a high-pressure homogenizer or an ultra-high-pressure homogenizer, a high-pressure collision type grinder, a ball mill, a bead mill, a disk type refiner, a conical refiner, a biaxial kneader, a vibration mill, a homomixer under high-speed rotation, an ultrasonic disperser, or a beater can be used. Among the above defibration treatment devices, it is more preferable to use a high-speed defibrator, a high-pressure homogenizer, or an ultra-high-pressure homogenizer, which are less affected by the grinding media and have less risk of contamination.
[0121] In the defibration process, for example, it is preferable to dilute the ionic substituent-introduced fiber with a dispersion medium to make it into a slurry state. As the dispersion medium, one or more selected from water and organic solvents such as polar organic solvents can be used. The polar organic solvent is not particularly limited, but for example, alcohols, polyhydric alcohols, ketones, ethers, esters, aprotic polar solvents, etc. are preferable. Examples of alcohols include methanol, ethanol, isopropanol, n-butanol, isobutyl alcohol, etc. Examples of polyhydric alcohols include ethylene glycol, propylene glycol, glycerin, etc. Examples of ketones include acetone, methyl ethyl ketone (MEK), etc. Examples of ethers include diethyl ether, tetrahydrofuran, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono n-butyl ether, propylene glycol monomethyl ether, etc. Examples of esters include ethyl acetate, butyl acetate, etc. Aprotic polar solvents include dimethylsulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAc), and N-methyl-2-pyrrolidinone (NMP).
[0122] The solid content concentration of the fine fibrous cellulose during the defibration treatment can be appropriately set. In addition, the slurry obtained by dispersing the ionic substituent-introduced fibers in a dispersion medium may contain solids other than the ionic substituent-introduced fibers, such as urea having hydrogen bonding properties.
[0123] (solvent) The dust dispersion inhibitor of the present invention contains a solvent. As the solvent, an organic solvent can be used in addition to an aqueous solvent. A mixed solvent of an aqueous solvent and an organic solvent can also be used.
[0124] Among them, the solvent is preferably a solvent mainly composed of water. That is, the solvent is preferably an aqueous solvent. In this specification, a solvent mainly composed of water is a solvent containing water in an amount of 50% by mass or more relative to the total mass of the solvent. The water content is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more relative to the total mass of the solvent. By using a solvent mainly composed of water as the solvent, the environmental load can be reduced. In addition, by using a solvent mainly composed of water, the safety of the worker who sprays the dust dispersion inhibitor can be more carefully considered.
[0125] When an organic solvent is used as the solvent, examples of the organic solvent include lower aliphatic alcohols such as methanol, ethanol, isopropanol, n-butanol, and isobutanol; ethylene glycol derivatives such as ethylene glycol, ethylene glycol monobutyl ether, and ethylene glycol monoethyl ether acetate; diethylene glycol derivatives such as diethylene glycol and diethylene glycol monobutyl ether; and diacetone alcohol. Examples of organic solvents include pyrrolidone compounds such as 2-pyrrolidone, 3-pyrrolidone, N-alkyl-2-pyrrolidone (e.g., N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-propyl-2-pyrrolidone), 5-alkyl-2-pyrrolidone (e.g., 5-methyl-2-pyrrolidone, 5-ethyl-2-pyrrolidone, 5-propyl-2-pyrrolidone), N-vinyl-2-pyrrolidone, and N-alkyl-3-pyrrolidone (e.g., N-methyl-3-pyrrolidone, N-ethyl-3-pyrrolidone, N-propyl-3-pyrrolidone); nitrogen-containing solvents such as formamide, N-methylformamide, N,N-dimethylformamide, N,N-diethylformamide, acetamide, N-methylacetamide, and N,N-dimethylacetamide; methyl alcohol, ethyl alcohol-based solvents such as diethyl ether, propyl alcohol, butyl alcohol, 1-propanol, 2-propanol, isopropyl alcohol, ethylene glycol, salicyl alcohol, cinnamyl alcohol, veraryl alcohol, cinnamyl alcohol, diphenylmethanol, vanillyl alcohol, benzyl alcohol, 2-methylbenzyl alcohol, 3-methylbenzyl alcohol, 3-nitrilebenzyl alcohol, 4-methylbenzyl alcohol, α-methylbenzyl alcohol, allyl alcohol, propargyl alcohol, phenethyl alcohol, hydroxybenzyl alcohol, and hydroxyphenethyl alcohol; and chlorine-based solvents such as chloroform, carbon tetrachloride, methylene chloride, trichloroethylene, and tetrachloroethylene.
[0126] The content of the solvent is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, based on the total mass of the dust dispersion inhibitor. The content of the solvent is preferably 99.99% by mass or less, more preferably 99.95% by mass or less, and even more preferably 99.90% by mass or less, based on the total mass of the dust dispersion inhibitor. By setting the content of the solvent within the above range, it becomes easier to obtain a dust dispersion inhibitor having a better dust dispersion prevention effect.
[0127] (optional ingredient) The dust dispersion inhibitor of the present invention may further contain optional components in addition to the above-mentioned components. Examples of the optional components include surfactants, inorganic layered compounds, inorganic acicular minerals, antifoaming agents, inorganic particles, organic particles, lubricants, antioxidants, UV absorbers, stabilizers, plasticizers, crosslinking agents, thickeners, etc. In addition, the dust dispersion inhibitor may contain hydrophilic polymers, hydrophilic low-molecular-weight compounds, organic ions, etc. as optional components.
[0128] Examples of the surfactant include anionic surfactants, cationic surfactants, nonionic surfactants, and amphoteric surfactants. Among these, examples of the anionic surfactant include sodium dodecylbenzenesulfonate, sodium lauryl sulfate, polyoxyethylene sodium lauryl sulfate, phosphate esters, α-olefin sulfonic acid, higher alcohol ethoxy sulfates, and dialkyl sulfosuccinates. Examples of the cationic surfactant include lauryl dimethyl benzyl ammonium chloride, and examples of the nonionic surfactant include polyoxyethylene nonylphenol ether and polyoxyethylene oleyl ether.
[0129] The hydrophilic polymer is preferably a hydrophilic oxygen-containing organic compound (excluding the above-mentioned fibrous cellulose), and examples of the oxygen-containing organic compound include polyethylene glycol, polyethylene oxide, casein, dextrin, starch, modified starch, polyvinyl alcohol, modified polyvinyl alcohol (acetoacetylated polyvinyl alcohol, etc.), polyvinylpyrrolidone, polyvinyl methyl ether, polyacrylates, acrylic acid alkyl ester copolymers, urethane copolymers, cellulose derivatives (hydroxyethyl cellulose, carboxyethyl cellulose, carboxymethyl cellulose, etc.), and the like.
[0130] The hydrophilic low molecular weight compound is preferably a hydrophilic oxygen-containing organic compound, more preferably a polyhydric alcohol, such as glycerin, sorbitol, or ethylene glycol.
[0131] Examples of organic ions include tetraalkylammonium ions and tetraalkylphosphonium ions. Examples of tetraalkylammonium ions include tetramethylammonium ions, tetraethylammonium ions, tetrapropylammonium ions, tetrabutylammonium ions, tetrapentylammonium ions, tetrahexylammonium ions, tetraheptylammonium ions, tributylmethylammonium ions, lauryltrimethylammonium ions, cetyltrimethylammonium ions, stearyltrimethylammonium ions, octyldimethylethylammonium ions, lauryldimethylethylammonium ions, didecyldimethylammonium ions, lauryldimethylbenzylammonium ions, and tributylbenzylammonium ions. Examples of tetraalkylphosphonium ions include tetramethylphosphonium ions, tetraethylphosphonium ions, tetrapropylphosphonium ions, tetrabutylphosphonium ions, and lauryltrimethylphosphonium ions. Examples of tetrapropylonium ions and tetrabutylonium ions include tetra-n-propylonium ions and tetra-n-butylonium ions, respectively.
[0132] The content of the optional components is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, based on the total mass of the dust-proofing agent.
[0133] (Method of manufacturing dust prevention agent) As the dust dispersion inhibitor, the dispersion obtained in the defibration process in the above-mentioned method for producing fine fibrous cellulose can be used as it is. The dispersion obtained in the defibration process contains water in addition to fibrous cellulose having a fiber width of 1000 nm or less. In this way, in the present invention, the dust dispersion inhibitor can be produced in the process for producing fine fibrous cellulose, making it possible to prevent dust dispersion in a simpler method. In addition, when the dust dispersion inhibitor contains the above-mentioned optional components, the optional components may be mixed into the dispersion obtained in the defibration process.
[0134] The dust dispersion inhibitor may be produced by redispersing in a solvent a concentrate or solid of fibrous cellulose having a fiber width of 1000 nm or less contained in the dispersion obtained in the above-mentioned defibration process. When the dust dispersion inhibitor is obtained through a process of redispersing in a solvent a concentrate or solid of fibrous cellulose having a fiber width of 1000 nm or less, a process of obtaining a concentrate of fibrous cellulose having a fiber width of 1000 nm or less is first provided. Examples of the process of obtaining a concentrate of fibrous cellulose having a fiber width of 1000 nm or less include a process of adding a flocculant such as a polyvalent metal salt to the dispersion containing fine fibrous cellulose obtained in the defibration process, and a process of adding an organic onium ion or a compound that forms an organic onium ion by neutralization.
[0135] When the step of obtaining a concentrate of fibrous cellulose having a fiber width of 1000 nm or less is a step of adding a flocculant such as a polyvalent metal salt, the step of adding a flocculant such as a polyvalent metal salt to the dispersion containing fine fibrous cellulose obtained in the defibration treatment step is included. In this case, the polyvalent metal salt is preferably added as an aqueous solution containing the polyvalent metal salt. Examples of the polyvalent metal salt include aluminum sulfate (aluminum sulfate), aluminum chloride, polyaluminum chloride, calcium chloride, magnesium chloride, calcium sulfate, magnesium sulfate, copper chloride, copper sulfate, iron chloride, iron sulfate, lead chloride, and lead sulfide.
[0136] The step of adding the polyvalent metal salt is also called the aggregation step because the fine fibrous cellulose is aggregated by the metal component. In the aggregation step, the metal salt containing the polyvalent metal is preferably added in an amount of 1 part by mass or more, more preferably 5 parts by mass or more, per 100 parts by mass of the fine fibrous cellulose contained in the dispersion. In addition, the metal salt containing the polyvalent metal is preferably added in an amount of 100 parts by mass or less, more preferably 50 parts by mass or less, per 100 parts by mass of the fine fibrous cellulose contained in the dispersion.
[0137] The flocculation step preferably further includes a filtration step after adding a polyvalent metal salt and stirring. By providing such a filtration step, a concentrate can be obtained. The filter medium used in the filtration step is not particularly limited, but filter mediums made of stainless steel, filter paper, polypropylene, nylon, polyethylene, polyester, etc. can be used. Since acid may be used, polypropylene filter medium is preferable. The lower the air permeability of the filter medium, the higher the yield. 3 / cm 2 sec or less, preferably 10 cm 3 / cm 2 sec or less, more preferably 1 cm 3 / cm 2 sec or less.
[0138] The filtration step may further include a compression step. In the compression step, a compression device may be used. As such a device, a general pressing device such as a belt press, a screw press, or a filter press may be used, and the device is not particularly limited. The pressure during compression is preferably 0.2 MPa or more, more preferably 0.4 MPa or more.
[0139] In addition, when the step of obtaining a concentrate of fibrous cellulose having a fiber width of 1000 nm or less is a step of adding an organic onium ion or a compound that forms an organic onium ion by neutralization, the method includes a step of adding an organic onium ion or a compound that forms an organic onium ion by neutralization to the fine fibrous cellulose-containing dispersion obtained in the defibration process. Specifically, the above-mentioned organic onium ion or a compound that forms an organic onium ion by neutralization is added to the fine fibrous cellulose-containing dispersion obtained in the above-mentioned defibration process. In this case, the organic onium ion is preferably added as a solution containing the organic onium ion, and more preferably as an aqueous solution containing the organic onium ion.
[0140] An aqueous solution containing an organic onium ion usually contains an organic onium ion and a counter ion (anion). When preparing an aqueous solution of an organic onium ion, if the organic onium ion and the corresponding counter ion have already formed a salt, the organic onium ion may be dissolved in water as is. When preparing an aqueous solution of an organic onium ion, if the organic onium ion and the corresponding counter ion have already formed a salt, the organic onium ion may be dissolved in water or hot water.
[0141] In addition, organic onium ions may be generated only after neutralization with an acid, such as dodecylamine. In this case, the organic onium ion is obtained by reacting a compound that forms an organic onium ion by neutralization with an acid. In this case, the acid used for neutralization may be an inorganic acid such as hydrochloric acid, sulfuric acid, or nitric acid, or an organic acid such as lactic acid, acetic acid, formic acid, or oxalic acid.
[0142] The step of adding organic onium ions or compounds that form organic onium ions by neutralization to the fine fibrous cellulose-containing slurry preferably further includes a stirring step. In the stirring step, the liquid temperature of the fine fibrous cellulose-containing slurry to which the organic onium ions have been added (hereinafter also referred to as stirring temperature) is preferably 60°C or less, more preferably 50°C or less, even more preferably 40°C or less, and particularly preferably 30°C or less. In the present invention, by setting the stirring temperature within the above range, the mobility of the organic onium ions can be controlled within an appropriate range, and thus the counter ion exchange in the fine fibrous cellulose can be sufficiently promoted.
[0143] The amount of organic onium ion added is preferably 2% by mass or more, more preferably 10% by mass or more, even more preferably 50% by mass or more, and particularly preferably 100% by mass or more, based on the total mass of the fine fibrous cellulose. The amount of organic onium ion added is preferably 1000% by mass or less, based on the total mass of the fine fibrous cellulose. The molar number of the organic onium ion to be added is preferably 0.2 times or more, more preferably 1.0 times or more, and even more preferably 2.0 times or more, the value obtained by multiplying the amount (molar number) of phosphorus oxo acid groups contained in the fine fibrous cellulose by the valence. The molar number of the organic onium ion to be added is preferably 10 times or less the value obtained by multiplying the amount (molar number) of phosphorus oxo acid groups contained in the fine fibrous cellulose by the valence.
[0144] When the organic onium ion is added and stirred, an aggregate is generated in the slurry containing fine fibrous cellulose. The aggregate is an aggregate of fine fibrous cellulose having an organic onium ion as a counter ion. The slurry containing fine fibrous cellulose in which the aggregate is generated is filtered under reduced pressure to recover the aggregate of fine fibrous cellulose.
[0145] The obtained fine fibrous cellulose aggregate may be washed with ion-exchanged water. By repeatedly washing the fine fibrous cellulose aggregate with ion-exchanged water, excess organic onium ions and the like contained in the fine fibrous cellulose aggregate can be removed.
[0146] The content of fibrous cellulose relative to the total mass of the fine fibrous cellulose concentrate obtained through the above-mentioned process is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more. The upper limit of the content of fibrous cellulose relative to the total mass of the fine fibrous cellulose concentrate is preferably 99% by mass.
[0147] When the manufacturing process of the dust dispersion inhibitor includes the step of obtaining the concentrate described above, a redispersion step is provided after the step of obtaining the concentrate. In the redispersion step, the fine fibrous cellulose concentrate is redispersed in a solvent. The solvent used for redispersion is preferably appropriately selected in consideration of the flocculant used in the concentration step. For example, when the concentrate is obtained by adding a polyvalent metal salt, an aqueous solution containing tetraalkylonium hydroxide or the like is preferred as the redispersion liquid, particularly tetraalkylammonium hydroxide and tetraalkylphosphonium hydroxide are preferred, and a use liquid containing tetraalkylammonium hydroxide is more preferred. Examples of the tetraalkylammonium hydroxide include tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, triethylmethylammonium hydroxide, tetrapentylammonium hydroxide, tetrahexylammonium hydroxide, tetraheptylammonium hydroxide, lauryltrimethylammonium hydroxide, cetyltrimethylammonium hydroxide, stearyltrimethylammonium hydroxide, octyldimethylethylammonium hydroxide, lauryldimethylethylammonium hydroxide, didecyldimethylammonium hydroxide, lauryldimethylbenzylammonium hydroxide, tributylbenzylammonium hydroxide, methyltri-n-octylammonium hydroxide, alkyldimethylbenzylammonium hydroxide, di-n-alkyldimethylammonium hydroxide, and behenyltrimethylammonium hydroxide.As the tetraalkylphosphonium hydroxide, it is preferable to select tetramethylphosphonium hydroxide, tetraethylphosphonium hydroxide, tetrapropylphosphonium hydroxide, tetrabutylphosphonium hydroxide, triethylmethylphosphonium hydroxide, tetraphenylphosphonium hydroxide, tetraoctylphosphonium hydroxide, acetonyltriphenylphosphonium hydroxide, allyltriphenylphosphonium hydroxide, amyltriphenylphosphonium hydroxide, benzyltriphenylphosphonium hydroxide, ethyltriphenylphosphonium hydroxide, or the like. In addition, when a concentrate is obtained by adding an organic onium ion, examples of the redispersion liquid include water, methanol, ethanol, n-propyl alcohol, isopropyl alcohol (IPA), 1-butanol, m-cresol, glycerin, acetic acid, pyridine, tetrahydrofuran (THF), acetone, methyl ethyl ketone (MEK), ethyl acetate, aniline, N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), hexane, cyclohexane, benzene, toluene, p-xylene, diethyl ether, and chloroform. These solvents may be used in combination. In the redispersion step, redispersion may be performed using the defibration treatment device used in the above-mentioned defibration treatment step.
[0148] After or during the step of redispersing the concentrate, the optional ingredients described above may be mixed.
[0149] (Method for preventing dust scattering) The present invention also relates to a method for preventing dust dispersion, which includes a step of spraying the above-mentioned dust dispersion inhibitor on a dust-generating object. In the dust dispersion prevention method, the dust dispersion inhibitor is sprayed on a dust-generating object such as soil or sand that is a dust source. In this way, the present invention can prevent dust dispersion by a simple method that includes a step of spraying the above-mentioned dust dispersion inhibitor on a dust-generating object.
[0150] There is no particular limit to the amount of dust-prevention agent to be spread, but the maximum amount is 500 g / m2 of the surface area of the object where dust is generated. 2 It is preferable to spray so that the amount is 1000 g / m or more. 2 By setting the coating amount of the dust-scattering inhibitor within the above range, the dust-scattering prevention effect is more effectively exhibited.
[0151] After spraying the dust dispersion prevention agent on the dust-generating object, it is preferable to provide a drying process. This allows the soil and sand that constitute the dust-generating object to be more firmly bound. There are no particular limitations on the drying conditions, but in normal weather other than rainy weather, it is sufficient to leave it overnight after spraying. EXAMPLES
[0152] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.
[0153] <Manufacturing example A> [Phosphate esterification] The raw pulp used was softwood kraft pulp (solid content 93% by mass, basis weight 208 g / m) manufactured by Oji Paper. 2 A sheet-like product (with a Canadian Standard Freeness (CSF) of 700 ml when disintegrated and measured in accordance with JIS P 8121) was used.
[0154] This raw pulp was subjected to phosphorylation treatment as follows. First, a mixed aqueous solution of ammonium dihydrogen phosphate and urea was added to 100 parts by mass (bone dry mass) of the raw pulp to adjust the composition to 45 parts by mass of ammonium dihydrogen phosphate, 120 parts by mass of urea, and 150 parts by mass of water, to obtain a chemical-impregnated pulp. Next, the obtained chemical-impregnated pulp was heated in a hot air dryer at 165°C for 200 seconds to introduce phosphoric acid groups into the cellulose in the pulp, to obtain a phosphorylated pulp.
[0155] The phosphorylated pulp was then washed. The washing was carried out by pouring 10 L of ion-exchanged water into 100 g (bone dry weight) of phosphorylated pulp to obtain a pulp dispersion, stirring the pulp to uniformly disperse it, and then repeatedly filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate reached 100 μS / cm or less.
[0156] Next, the phosphorylated pulp after washing was subjected to a neutralization treatment as follows. First, the phosphorylated pulp after washing was diluted with 10 L of ion-exchanged water, and then a 1N aqueous solution of sodium hydroxide was added little by little while stirring to obtain a phosphorylated pulp slurry having a pH of 12 to 13. Next, the phosphorylated pulp slurry was dehydrated to obtain a phosphorylated pulp that had been subjected to a neutralization treatment. Next, the above-mentioned washing treatment was performed on the phosphorylated pulp after the neutralization treatment.
[0157] The infrared absorption spectrum of the phosphorylated pulp obtained was measured using FT-IR. -1 Absorption due to phosphate groups was observed around 2θ = 14° to 17° and 2θ = 22° to 23°, confirming that phosphate groups had been added to the pulp. When the obtained phosphorylated pulp was analyzed using an X-ray diffractometer, typical peaks were observed at two positions, around 2θ = 14° to 17° and 2θ = 22° to 23°, confirming that it had cellulose type I crystals.
[0158] Ion-exchanged water was added to the obtained phosphorylated pulp to prepare a slurry with a solid content of 2% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a dispersion containing fine fibrous cellulose.
[0159] X-ray diffraction confirmed that this fine fibrous cellulose maintained cellulose type I crystals. The fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3 to 5 nm. The number average aspect ratio was calculated by extracting 100 pieces of fine fibrous cellulose from AFM image analysis, and found to be 300. The amount of phosphate groups (amount of strongly acidic groups) measured by the measurement method described below was 1.45 mmol / g.
[0160] The fine fibrous cellulose-containing dispersion obtained in this production example was diluted with ion-exchanged water to adjust the solid content concentration of the fine fibrous cellulose to 0.4 mass %. The dispersion was used as a dust dispersion inhibitor A.
[0161] <Manufacturing example B> [Phosphate esterification] Phosphorylated pulp was obtained in the same manner as in Production Example A. Ion-exchanged water was added to the obtained phosphorylated pulp to prepare a slurry with a solid content concentration of 2% by mass. The mixture was treated once with a high-pressure homogenizer (Beryu-Mini, manufactured by Biryu Co., Ltd.) at a pressure of 100 MPa to obtain a fine fibrous cellulose-containing dispersion containing fine fibrous cellulose. When the obtained fine fibrous cellulose-containing dispersion was observed with an optical microscope, a large number of fibrous celluloses with a fiber width of 20 μm or more were observed. On the other hand, when the obtained fine fibrous cellulose-containing dispersion was measured with a transmission electron microscope, a large number of fine fibrous celluloses with a fiber width of 3 to 5 nm were also observed. When 100 pieces of fine fibrous cellulose were extracted from image analysis by AFM and the number average value of the aspect ratio was calculated, the number average value of the aspect ratio was 225.
[0162] The fine fibrous cellulose-containing dispersion obtained in this production example was diluted with ion-exchanged water to adjust the solid content concentration of the fine fibrous cellulose to 0.4 mass %. The dispersion was used as a dust dispersion inhibitor B.
[0163] <Manufacturing example C> [Phosphite esterification] A phosphited pulp was obtained by the same procedure as in Production Example A, except that 33 parts by mass of phosphorous acid (phosphonic acid) was used instead of ammonium dihydrogen phosphate.
[0164] The infrared absorption spectrum of the obtained phosphorous pulp was measured using FT-IR. -1 Absorption due to the P=O of the phosphonic acid group, which is a tautomer of the phosphorous acid group, was observed near the nucleus, confirming that the phosphorous acid group (phosphonic acid group) was added to the pulp. In addition, when the obtained phosphorous-containing pulp was analyzed using an X-ray diffraction device, typical peaks were confirmed at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°, confirming that it has cellulose type I crystals.
[0165] The resulting phosphorous-subtilized pulp was treated in a wet pulverizer in the same manner as in Production Example A to obtain a fine fibrous cellulose-containing dispersion liquid containing fine fibrous cellulose.
[0166] X-ray diffraction confirmed that this fine fibrous cellulose maintained cellulose type I crystals. The fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3 to 5 nm. The number average aspect ratio was calculated by extracting 100 pieces of fine fibrous cellulose from image analysis using AFM, and the number average aspect ratio was found to be 280. The amount of phosphorous acid groups (amount of first dissociated acid) measured by the measurement method described below was 1.51 mmol / g. The total amount of dissociated acid was 1.54 mmol / g.
[0167] The fine fibrous cellulose-containing dispersion obtained in this production example was diluted with ion-exchanged water to adjust the solid content concentration of the fine fibrous cellulose to 0.4 mass %. The dispersion was used as dust dispersion inhibitor C.
[0168] <Manufacturing example D> [TEMPO oxidation] As the raw material pulp, softwood kraft pulp (undried) manufactured by Oji Paper Co., Ltd. was used. The raw material pulp equivalent to 100 parts by weight of dry mass, 1.6 parts by weight of TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl), and 10 parts by weight of sodium bromide were dispersed in 10,000 parts by weight of water. Next, a 13% by weight aqueous solution of sodium hypochlorite was added to 10 mmol per 1.0 g of pulp to start the reaction. During the reaction, a 0.5 M aqueous solution of sodium hydroxide was added dropwise to keep the pH at 10 to 10.5, and the reaction was deemed to be complete when no change in pH was observed.
[0169] The TEMPO oxidized pulp was then washed. The washing was performed by dehydrating the pulp slurry after TEMPO oxidation to obtain a dehydrated sheet, pouring 5,000 parts by mass of ion-exchanged water into the sheet, stirring to disperse the sheet uniformly, and then filtering and dehydrating the sheet. The washing was completed when the electrical conductivity of the filtrate reached 100 μS / cm or less.
[0170] In addition, the obtained TEMPO oxidized pulp was analyzed using an X-ray diffraction device, and typical peaks were confirmed at two positions, around 2θ = 14° to 17° and around 2θ = 22° to 23°, confirming the presence of cellulose type I crystals.
[0171] Ion-exchanged water was added to the obtained TEMPO oxidized pulp to prepare a slurry with a solid content of 2% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a dispersion containing fine fibrous cellulose.
[0172] X-ray diffraction confirmed that this fine fibrous cellulose maintained cellulose type I crystals. The fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3 to 5 nm. The number average aspect ratio was calculated by extracting 100 pieces of fine fibrous cellulose from image analysis using AFM, and found to be 250. The amount of carboxy groups measured by the measurement method described below was 1.80 mmol / g.
[0173] The fine fibrous cellulose-containing dispersion obtained in this production example was diluted with ion-exchanged water to adjust the solid content concentration of the fine fibrous cellulose to 0.4 mass %. The dispersion was used as dust dispersion inhibitor D.
[0174] <Production Example E> [Carboxymethylation (CM)] Carboxymethylated pulp was produced by the method described in Production Example 1 of WO 2014 / 088072, except that softwood kraft pulp (undried) manufactured by Oji Paper was used as the raw material pulp.
[0175] The resulting carboxymethylated pulp was then subjected to a washing treatment. The washing treatment was carried out by dehydrating the carboxymethylated pulp slurry to obtain a dehydrated sheet, pouring 5,000 parts by mass of ion-exchanged water into the sheet, stirring to disperse the sheet uniformly, and then repeatedly filtering and dehydrating the sheet. The washing was completed when the electrical conductivity of the filtrate reached 100 μS / cm or less.
[0176] Ion-exchanged water was added to the obtained carboxymethylated pulp to prepare a slurry having a solid content of 2% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a dispersion containing fine fibrous cellulose.
[0177] X-ray diffraction confirmed that this fine fibrous cellulose maintained cellulose type I crystallinity. In addition, AFM image analysis was used to extract 100 pieces of fine fibrous cellulose and calculate the number average aspect ratio, which was found to be 190.
[0178] The fine fibrous cellulose-containing dispersion obtained in this production example was diluted with ion-exchanged water to adjust the solid content concentration of the fine fibrous cellulose to 0.4 mass %. The dispersion was used as dust dispersion inhibitor E.
[0179] <Manufacturing example F> [Sulfate esterification] A sulfated pulp was obtained by the same procedure as in Production Example A, except that 38 parts by mass of amidosulfuric acid was used instead of ammonium dihydrogen phosphate and the heating time was extended to 19 minutes.
[0180] The infrared absorption spectrum of the sulfated pulp obtained was measured using FT-IR. -1 Absorption due to sulfate groups (sulfur oxoacid groups) was observed near the 2θ angle, confirming that sulfate groups (sulfur oxoacid groups) had been added to the pulp. In addition, when the obtained sulfated pulp was analyzed using an X-ray diffractometer, typical peaks were confirmed at two positions, near 2θ = 14° to 17° and near 2θ = 22° to 23°, confirming that it had cellulose type I crystals. The amount of sulfate groups (sulfur oxoacid groups) measured by the measurement method described below was 1.12 mmol / g.
[0181] The obtained sulfated pulp was added with ion-exchanged water and stirred to prepare a slurry with a solid content of 2% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a dispersion containing fine fibrous cellulose. In addition, 100 pieces of fine fibrous cellulose were extracted from the image analysis by AFM, and the number average value of the aspect ratio was calculated, and the number average value of the aspect ratio was 280.
[0182] The fine fibrous cellulose-containing dispersion obtained in this production example was diluted with ion-exchanged water to adjust the solid content concentration of the fine fibrous cellulose to 0.4 mass %. The dispersion was used as dust dispersion inhibitor F.
[0183] <Manufacturing example G> [Non-modified] As the raw material pulp, softwood kraft pulp (undried) manufactured by Oji Paper Co., Ltd. was used. The raw material pulp was added with ion-exchanged water, diluted to a solid content concentration of 2% by mass, and then subjected to a refiner treatment and beaten (pre-defibrated) until the Canadian standard freeness (CSF) measured according to JIS P 8121 was 50 mL or less. Ion-exchanged water was further added to the pulp dispersion after pre-defibration, diluted to a solid content concentration of 0.5% by mass, and then treated twice with a high-pressure homogenizer "Starburst" manufactured by Sugino Machine Co., Ltd. at a treatment pressure of 200 MPa to obtain a dispersion containing fine fibrous cellulose. The number-average fiber width of the fine fibrous cellulose contained in the dispersion was 1000 nm or less, but it was visually confirmed that the fibrous matter remained because the fine cellulose had not been completely defibrated. The fine fibrous cellulose contained in the dispersion was unmodified fine fibrous cellulose after mechanical defibration. In addition, 100 fine fibrous cellulose samples were extracted from AFM images and the number average aspect ratio was calculated, which was found to be 97.
[0184] The dispersion containing the mechanically defibrated unmodified fine fibrous cellulose obtained in this production example was diluted with ion-exchanged water to adjust the solid content concentration of the mechanically defibrated unmodified fine fibrous cellulose to 0.4 mass %. The dispersion was used as dust dispersion inhibitor G.
[0185] <Manufacturing example H> [Hypochlorous acid oxidation (NaClO oxidation)] A sheet (solid content 90% by mass) made from bleached softwood kraft pulp (NBKP) was mixed with a hand mixer (Osaka Chemical, Labo Millser PLUS) at 20,000 rpm for 15 seconds to produce a cotton-like fluffed pulp (solid content 90% by mass). Sodium hypochlorite pentahydrate was then added to ion-exchanged water to prepare an aqueous solution with a sodium hypochlorite solid content of 22% by mass. 9,000 parts by mass of a 22% aqueous sodium hypochlorite solution was added to 100 parts by mass of the cotton-like fluffed pulp, and the mixture was reacted for 2 hours in a warm bath at 30°C to obtain a carboxyl-introduced pulp. During the reaction, a 1N aqueous sodium hydroxide solution was added appropriately to maintain the pH at 11.
[0186] Next, the obtained carboxyl-group-introduced pulp was subjected to a washing treatment. The washing treatment was carried out by repeatedly pouring ion-exchanged water into the obtained carboxyl-group-introduced pulp, stirring the obtained pulp dispersion so that the pulp was uniformly dispersed, and then filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate became 100 μS / cm or less.
[0187] The obtained carboxyl-introduced pulp was analyzed using an X-ray diffraction device, and typical peaks were confirmed at two positions, around 2θ = 14° to 17° and around 2θ = 22° to 23°, confirming the presence of cellulose type I crystals.
[0188] Ion-exchanged water was added to the obtained carboxyl group-introduced pulp to prepare a slurry with a solid content of 2% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a dispersion containing fine fibrous cellulose.
[0189] X-ray diffraction confirmed that the obtained fine fibrous cellulose maintained cellulose type I crystals. In addition, the fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3 to 5 nm. The number average aspect ratio was calculated by extracting 100 pieces of fine fibrous cellulose from AFM image analysis, and the number average aspect ratio was found to be 89. The amount of carboxyl groups measured by the measurement method described below was 0.70 mmol / g.
[0190] <Manufacturing example I> [Maleic acid esterification] A sheet (solid content concentration 90% by mass) made from bleached softwood kraft pulp (NBKP) was mixed with a hand mixer (Osaka Chemical, Labo Millser PLUS) at a rotation speed of 20,000 rpm for 15 seconds to produce a cotton-like fluffed pulp (solid content concentration 90% by mass). An autoclave was filled with 100 parts by mass of the cotton-like fluffed pulp and 50 parts by mass of maleic anhydride, and treated at 150°C for 2 hours to obtain a carboxyl group-introduced pulp.
[0191] Next, the obtained carboxyl-group-introduced pulp was subjected to a washing treatment. The washing treatment was carried out by repeatedly pouring ion-exchanged water into the obtained carboxyl-group-introduced pulp, stirring the obtained pulp dispersion so that the pulp was uniformly dispersed, and then filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate became 100 μS / cm or less.
[0192] The infrared absorption spectrum of the obtained carboxyl-introduced pulp was measured using FT-IR. -1 Absorption due to carboxyl groups was observed near the 2θ angle, confirming that the pulp had been maleated. When the carboxyl-introduced pulp was analyzed using an X-ray diffractometer, typical peaks were observed at two positions, near 2θ = 14° to 17° and near 2θ = 22° to 23°, confirming that the cellulose had type I crystals.
[0193] Ion-exchanged water was added to the obtained carboxyl group-introduced pulp to prepare a slurry with a solid content of 2% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a dispersion containing fine fibrous cellulose.
[0194] X-ray diffraction confirmed that the obtained fine fibrous cellulose maintained cellulose type I crystals. In addition, the fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3 to 5 nm. From image analysis using AFM, 100 pieces of fine fibrous cellulose were extracted and the number average aspect ratio was calculated, which was found to be 180. The amount of carboxyl groups measured by the measurement method described below was 1.22 mmol / g.
[0195] <Manufacturing example J> [Carboxyethylation (CE)] The raw pulp used was softwood kraft pulp (solid content 93% by mass, basis weight 245 g / m) manufactured by Oji Paper. 2 A sheet-like product (with a Canadian Standard Freeness (CSF) of 700 ml when disintegrated, measured in accordance with JIS P 8121-2:2012) was used.
[0196] To 100 parts by mass (bone dry mass) of this raw pulp, 250 parts by mass of 12N NaOH aqueous solution, 163 parts by mass of 2-chloropropionic acid, and 140 parts by mass of ion-exchanged water (total 553 parts by mass) were added to obtain a chemical-impregnated pulp. The obtained chemical-impregnated pulp was then heated in a hot air dryer at 165°C for 10 minutes to introduce carboxyethyl groups (carboxy groups) into the cellulose in the pulp, thereby obtaining a carboxy-group-introduced pulp.
[0197] Next, the obtained carboxyl-group-introduced pulp was subjected to a washing treatment. The washing treatment was carried out by repeatedly pouring ion-exchanged water into the obtained carboxyl-group-introduced pulp, stirring the obtained pulp dispersion so that the pulp was uniformly dispersed, and then filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate became 100 μS / cm or less.
[0198] Next, the washed carboxyl-introduced pulp was neutralized as follows: First, the washed carboxyl-introduced pulp was diluted with 10 L of ion-exchanged water, and then a 1N aqueous sodium hydroxide solution was added little by little while stirring to obtain a carboxyl-introduced pulp slurry having a pH of 12 to 13. Next, the carboxyl-introduced pulp slurry was dehydrated and washed to obtain a neutralized carboxyl-introduced pulp.
[0199] When the carboxyl-group-introduced pulp was analyzed using an X-ray diffraction device, typical peaks were confirmed at two positions, around 2θ = 14° to 17° and around 2θ = 22° to 23°, confirming the presence of cellulose type I crystals.
[0200] Ion-exchanged water was added to the obtained carboxyl group-introduced pulp to prepare a slurry with a solid content of 2% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a dispersion containing fine fibrous cellulose.
[0201] X-ray diffraction confirmed that the obtained fine fibrous cellulose maintained cellulose type I crystals. In addition, the fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3-5 nm. The number average aspect ratio was calculated by extracting 100 pieces of fine fibrous cellulose from AFM image analysis, and the number average aspect ratio was found to be 200. The amount of carboxyl groups measured by the measurement method described below was 1.41 mmol / g.
[0202] <Manufacturing example K> [Sulfoethylation] The raw pulp used was softwood kraft pulp (solid content 93% by mass, basis weight 245 g / m) manufactured by Oji Paper. 2 A sheet-like product (with a Canadian Standard Freeness (CSF) of 700 ml when disintegrated, measured in accordance with JIS P 8121-2:2012) was used.
[0203] A chemical solution (total 960 parts by mass) consisting of 180 parts by mass of 2N NaOH aqueous solution and 780 parts by mass of 25% by mass sodium vinyl sulfonate aqueous solution was added to 100 parts by mass (bone dry mass) of this raw pulp to obtain a chemical solution-impregnated pulp. The obtained chemical solution-impregnated pulp was then heated in a hot air dryer at 165°C for 16 minutes to introduce sulfoethyl groups (sulfone groups) into the cellulose in the pulp, thereby obtaining a sulfoethyl group-introduced pulp (sulfone group-introduced pulp).
[0204] Next, the obtained sulfoethyl group-introduced pulp was subjected to a washing treatment. The washing treatment was carried out by repeatedly pouring ion-exchanged water into the obtained sulfoethyl group-introduced pulp, stirring the obtained pulp dispersion so that the pulp was uniformly dispersed, and then filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate became 100 μS / cm or less.
[0205] The amount of sulfoethyl groups (amount of sulfone groups) of the obtained sulfoethyl group-introduced pulp, measured by the measurement method described below, was 1.48 mmol / g. In addition, when the sulfoethyl group-introduced pulp was analyzed using an X-ray diffractometer, typical peaks were confirmed at two positions, around 2θ = 14° to 17° and around 2θ = 22° to 23°, and it was confirmed that it had cellulose type I crystals.
[0206] Ion-exchanged water was added to the obtained sulfoethyl group-introduced pulp to prepare a slurry with a solid content of 2% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose-containing dispersion liquid containing fine fibrous cellulose.
[0207] X-ray diffraction confirmed that the obtained fine fibrous cellulose maintained cellulose type I crystals. In addition, the fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3-5 nm. Image analysis using AFM was used to extract 100 fine fibrous cellulose fibers and calculate the number average aspect ratio, which was found to be 230.
[0208] <Manufacturing example L> [Cationization treatment] The raw pulp used was softwood kraft pulp (solid content 93% by mass, basis weight 245 g / m) manufactured by Oji Paper. 2 A sheet-like product (with a Canadian Standard Freeness (CSF) of 700 ml when disintegrated, measured in accordance with JIS P 8121-2:2012) was used.
[0209] To 100 parts by mass (bone dry mass) of this raw pulp, 180 parts by mass of 1N NaOH aqueous solution and 325 parts by mass of a cationizing agent (Catiomaster G, Yokkaichi Synthetic Co., Ltd., glycidyl trimethylammonium chloride, pure content 73.1% by mass, moisture content 20.2% by mass) were added (total 505 parts by mass) to obtain a chemical solution-impregnated pulp. The obtained chemical solution-impregnated pulp was then heated in a hot air dryer at 165°C for 12 minutes to introduce cationic groups into the cellulose in the pulp, and a cationic group-introduced pulp was obtained.
[0210] Next, the obtained cationic group-introduced pulp was subjected to a washing treatment. The washing treatment was carried out by repeatedly pouring ion-exchanged water into the obtained cationic group-introduced pulp to obtain a pulp dispersion, stirring the pulp so that the pulp was uniformly dispersed, and then filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate became 100 μS / cm or less.
[0211] Next, the washed cationic group-introduced pulp was neutralized as follows: First, the washed cationic group-introduced pulp was diluted with 10 L of ion-exchanged water, and then 1N hydrochloric acid was added little by little while stirring to obtain a cationic group-introduced pulp slurry having a pH of 1 to 2. Next, the cationic group-introduced pulp slurry was dehydrated and washed to obtain a cationic group-introduced pulp that had been subjected to a neutralization treatment.
[0212] The resulting cationic group-introduced pulp was subjected to a trace nitrogen analysis, and the amount of cationic groups was calculated using the following formula, which was 1.45 mmol / g. The cationic group-introduced pulp was also analyzed using an X-ray diffractometer, and typical peaks were confirmed at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°, confirming the presence of cellulose type I crystals. (Amount of cationic groups) [mmol / g] = (amount of nitrogen) / 14 × 1000 / (amount of cationic group-introduced pulp used)
[0213] Ion-exchanged water was added to the obtained cationic group-introduced pulp to prepare a slurry with a solid content of 2% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a dispersion containing fine fibrous cellulose.
[0214] X-ray diffraction confirmed that the obtained fine fibrous cellulose maintained cellulose type I crystals. In addition, the fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3-5 nm. Image analysis using AFM was used to extract 100 fine fibrous cellulose fibers and calculate the number average aspect ratio, which was found to be 180.
[0215] The fine fibrous cellulose-containing dispersions obtained in Production Examples H to L were diluted with ion-exchanged water to adjust the solid content concentration of the fine fibrous cellulose to 0.4 mass %. The resulting dispersions were designated as dust dispersion inhibitors H to L, respectively.
[0216] [Measurement of phosphorus oxoacid group content] In measuring the amount of phosphorus oxoacid groups (amount of phosphoric acid groups or amount of phosphorous acid groups) of fibrous cellulose, ion-exchanged water was first added to the target fibrous cellulose to prepare a slurry with a solid content of 0.2% by mass. The resulting dispersion containing fine fibrous cellulose was treated with an ion-exchange resin, and then titrated with an alkali to measure the amount. Treatment with ion exchange resin was carried out by adding 1 / 10 by volume of a strongly acidic ion exchange resin (Amberjet 1024; Organo Corporation, conditioned) to the above-mentioned fine fibrous cellulose-containing dispersion, shaking for 1 hour, and then pouring onto a mesh with 90 μm openings to separate the resin and the slurry. The titration using alkali was performed by adding 10 μL of 0.1N sodium hydroxide solution every 5 seconds to the dispersion containing fine fibrous cellulose after the treatment with ion exchange resin, and measuring the change in the pH value of the slurry. The titration was performed while blowing nitrogen gas into the slurry 15 minutes before the start of the titration. In this neutralization titration, two points were observed where the increment (the differential value of pH with respect to the amount of alkali added) was maximum on the curve plotting the measured pH against the amount of alkali added. Of these, the first maximum point of the increment obtained after the start of the addition of alkali is called the first end point, and the second maximum point of the increment obtained next is called the second end point (Figure 1). The amount of alkali required from the start of the titration to the first end point is equal to the amount of first dissociated acid in the slurry used for the titration. The amount of alkali required from the start of the titration to the second end point is equal to the total amount of dissociated acid in the slurry used for the titration. The amount of alkali (mmol) required from the start of titration to the first end point was divided by the solid content (g) in the slurry to be titrated, and this value was taken as the amount of phosphorus oxoacid groups (mmol / g).
[0217] [Measurement of Carboxy Group Amount] In measuring the amount of carboxy groups in fibrous cellulose, ion-exchanged water was first added to the target fibrous cellulose to prepare a slurry with a solid content of 0.2% by mass. The resulting dispersion containing fine fibrous cellulose was treated with an ion-exchange resin, and then titrated with an alkali to measure the amount of carboxy groups. Treatment with ion exchange resin was carried out by adding 1 / 10 by volume of a strongly acidic ion exchange resin (Amberjet 1024; Organo Corporation, conditioned) to the above-mentioned fine fibrous cellulose-containing dispersion, shaking for 1 hour, and then pouring onto a mesh with 90 μm openings to separate the resin and the slurry. The titration using alkali was carried out by adding 50 μL of 0.1 N sodium hydroxide solution once every 30 seconds to the dispersion containing fine fibrous cellulose after the treatment with ion exchange resin, while measuring the change in pH value of the dispersion. The amount of carboxyl groups (mmol / g) was calculated by dividing the amount of alkali (mmol) required in the region corresponding to the first region shown in Figure 2 by the solid content (g) in the slurry to be titrated.
[0218] [Measurement of the amount of sulfur oxoacid group or sulfone group] The amount of sulfur oxoacid groups or sulfone groups in the fibrous cellulose was measured as follows. The fibrous cellulose obtained in Production Example F was frozen in a freezer and then dried for 3 days in a freeze dryer (FreeZone, manufactured by Labconco). The freeze-dried product was pulverized into a powder form using a hand mixer (Labo Millser PLUS, manufactured by Osaka Chemical) at a rotation speed of 20,000 rpm for 60 seconds. The freeze-dried and pulverized samples were subjected to pressure heating decomposition with nitric acid in a closed vessel. The samples were then appropriately diluted and the amount of sulfur was measured by ICP-OES. The value calculated by dividing the value by the bone dry mass of the fine fibrous cellulose used was taken as the amount of sulfur oxoacid groups or sulfonic groups (unit: mmol / g) of the fine fibrous cellulose.
[0219] <Examples 1 to 12> The dust-preventing agents of the production examples shown in Tables 1 and 2 were used to evaluate the dust-preventing effect.
[0220] <pH measurement> The pH at 25°C of the dust scattering preventives of each example was measured using a portable water quality meter D52 (manufactured by HORIBA, Ltd.).
[0221] <Preparation of evaluation sample (object generating dust)> As a model substance for generating dust, No. 6 silica sand (manufactured by Toyo Materia Co., Ltd.) was used. 5 g of this silica sand was laid in the center of a filter paper with a diameter of 90 mm so as to form a circular shape with a diameter of 50 mm, and used as an evaluation sample (object generating dust).
[0222] <Evaluation of spray characteristics> Approximately 7 g of the dust scattering preventives of each example was sprayed onto the evaluation sample (object generating dust) using a commercially available spray. At this time, the spray characteristics of each dust scattering preventive were evaluated based on the following criteria. A: Can be sprayed in a mist form and uniform spraying is possible B: Some clogging occurs, but spraying itself is possible C: Cannot be sprayed in a mist form and uniform spraying is difficult In addition, the evaluation sample (object generating dust) after the above spraying was dried at room temperature for 24 hours, and the adhesion force described later was evaluated.
[0223] <Evaluation of adhesion force of silica sand (evaluation of dust scattering prevention effect)> The central part of the evaluation sample (object generating dust) after the above drying was pushed in with a load of 2 N using a force tester MCT1150 (A&D Co., Ltd.), and the adhesion force of the silica sand in each object generating dust was evaluated based on the following criteria. A: The surface of the silica sand does not collapse and no cracks occur B: Some cracks occur, but the surface of the silica sand does not collapse C: A large number of cracks occur and the surface of the silica sand completely collapses If the above rating was A, the silica sand did not scatter at all even when blown with air from a commercially available dryer, and a dust scattering prevention effect was observed. If the above rating was B, a small amount of silica sand scattered when blown with air from a commercially available dryer, but a certain degree of dust scattering prevention effect was observed. On the other hand, if the above rating was C, the silica sand scattered when blown with air from a dryer in the same way.
[0224] <Comparative Example 1> As a dust dispersion prevention agent, a 0.4 mass % aqueous solution of sodium carboxymethylcellulose (manufactured by Tokyo Chemical Industry Co., Ltd.) was used, and the dust dispersion prevention effect was evaluated in the same manner as in the examples.
[0225] <Comparative Example 2> A 0.4 mass % aqueous solution of guar gum (manufactured by Wako Pure Chemical Industries, Ltd.) was used as the dust dispersion prevention agent, and the dust dispersion prevention effect was evaluated in the same manner as in the examples.
[0226] <Comparative Example 3> A 0.4 mass % aqueous solution of xanthan gum (manufactured by Tokyo Chemical Industry Co., Ltd.) was used as the dust dispersion prevention agent, and the dust dispersion prevention effect was evaluated in the same manner as in the examples.
[0227] <Comparative Example 4> A 0.4 mass % aqueous solution of chitosan (manufactured by Fuji Engineering Co., Ltd.) was used as the dust scattering prevention agent, and the dust scattering prevention effect was evaluated in the same manner as in the examples.
[0228] [Table 1]
[0229] [Table 2]
[0230] [Table 3]
[0231] The dust dispersion inhibitor used in the examples showed excellent spray characteristics. The dust dispersion inhibitor used in the examples also showed sufficient silica sand binding strength, and showed dust dispersion prevention effects. This is presumably because, in the examples, the dispersion of the fine fibrous cellulose caused the silica sand particles to be firmly bound by the crystalline fine fibrous cellulose, and a sufficient silica sand binding strength was developed to obtain the dust dispersion prevention effect. In particular, in Examples 1, 3 to 6, and 9 to 12, both the spray characteristics and the binding strength of the silica sand were good, and it was shown that they were more suitable as dust dispersion inhibitors. This is presumably due to the fact that the fiber diameter of the fine fibrous cellulose contained in Examples 1, 3 to 6, and 9 to 12 was smaller and the aspect ratio was larger. In addition, in the examples, the content of the fine fibrous cellulose in the dust dispersion inhibitor was 0.4 mass%, and it was found that even when the additive was at a low concentration, a sufficient dust dispersion inhibitor effect was exhibited. Thus, the dust dispersion inhibitors of the examples were dust dispersion inhibitors with excellent environmental compatibility, which could obtain a high dust dispersion inhibitor effect by using only a small amount of fine fibrous cellulose, which is a fine fiber derived from plants.
[0232] On the other hand, in the comparative examples, sufficient dust scattering prevention effect was not achieved. First, in the comparative examples 1 to 3, the silica sand was easily disintegrated in the evaluation test of the binding strength of the silica sand, and the dust scattering prevention effect was not achieved at all. On the other hand, when chitosan was used in the comparative example 4, the spray characteristics were poor and uniform dispersion was difficult, and it was not suitable as a dust scattering prevention agent. In addition, since chitosan dissolves only in weak acids, when chitosan is used as a dust scattering prevention agent, a weak acid agent must be sprayed on the soil. However, in terms of environmental load, it is naturally preferable that the agent to be sprayed on the soil has a pH close to neutral, and from the viewpoint of pH, it is not preferable to use chitosan.
Claims
1. A solvent and fibrous cellulose having a fiber width of 1000 nm or less, A spray coating agent in which the fibrous cellulose is unmodified fine fibrous cellulose, or the fibrous cellulose has at least one ionic substituent selected from the group consisting of a phosphorus oxoacid group, a substituent derived from a phosphorus oxoacid group, a carboxy group, a substituent derived from a carboxy group, a carboxyethyl group, a sulfur oxoacid group, a substituent derived from a sulfur oxoacid group, a sulfone group, a substituent derived from a sulfone group, and an ammonium group.
2. 2. The spray coating agent according to claim 1, wherein the fibrous cellulose has an aspect ratio of 10 or more.
3. The spray coating agent according to claim 1 or 2, wherein the solids concentration of the fibrous cellulose is 1.0 mass % or less.
4. The spray coating agent according to any one of claims 1 to 3, having a pH of 5.0 or more and 9.0 or less.
5. The spray coating agent according to any one of claims 1 to 4, wherein the solvent is a solvent containing water as a main component.
Citation Information
Patent Citations
Paint for coating open-air stockpile
JP1983117270A
Sprayable composition and method for forming outdoor foam protective coating
JP1996505600A
Method for forming daily protection cover for waste by spray
JP2000263010A
Method for forming coating layer
JP2003117515A
Dust-proof agent and dust-proofing method
JP2003126797A